Structure-based virtual screening identifies dicoumarol as a potent InhA inhibitor against Nocardia seriolae infection in largemouth bass (Micropterus salmoides) - Jin-Lai Gu; Chen-Wang Lu; Lin-Feng Kuang; Jie He; Zheng-Ran Jian; Yuan-Chang Gao; Sheng Lian; Shang-Jie Bai; Zheng-Yang Zhou; Ming-Zhu Liu; Peng-Fei Li; Er-Long Wang; et al. (Aquaculture, 2027)

SMART-guided discovery of anti-adipogenic guaiane sesquiterpenoids from the roots of Edgeworthia gardneri - Ming-Cui Yang; Lin-Lin Tian; Xiu-Qing Song; Yao-Yue Fan (Phytochemistry, 2026)

Tirzepatide improves neutrophilic inflammation in obese asthmatic mice by downregulating Th17 cell differentiation - Lu Sun; Su-Yan Yao; Zhong-Fu Zuo; Sheng-Xue Yu; Hong-Dan Yu; Qing-Lin Sun; Han-Song Zheng; Yang Hou; Si-Jing Lu; Tie-Feng Yao (Molecular Biology Reports, 2026)

Divergent formation pathways of soil particulate and mineral-associated organic carbon across soil depths under conservation tillage - Hong-Xuan Duan; Yu-Gang Tian; Cheng-Ze Yang; Qing Luo; Yang Liu; Zhi-Yan Hou; Rattan Lal; Yash Pal Dang; Zhi Dong; Xin Zhao; Hai-Lin Zhang (Applied Soil Ecology, 2026)

Bushen Yijing formula exerts chondroprotective effects in knee osteoarthritis via the ERα/PI3K/AKT signaling pathway: Insights from network pharmacology and experimental validation - Yu-Qing Zhai; Jian-Wei Lu; Qiang Yan; Jia-Wei Du; Yang-Shuo Ge; Min-Jun Zhao; Jian-Li Yin; Chun-Meng Huang; Ting-Ting Meng; Xin-Hui Huang; Liao-Lin Chen; Jia-Hui Luo; et al. (Tissue and Cell, 2026)

A review on the formation mechanisms, influencing factors, and applications of the cold-induced gel of egg white protein - Yanqiu Ma; Lin Lin; Qing Liu; Xiaoxue Yang; Xin Gao; Yaotong Liu; Huajiang Zhang; Lifeng Wang (Food Hydrocolloids, 2026)

Modeling the cooling effects of urban rivers on surrounding built-up areas via a SOMUCH-based scaled outdoor experiment - Lin Liu; Xin Feng; Jian Hang; Jiajia Hua; Guanwen Chen; Qing Wu; Na Zhao; Yuguang Zhao; Yuling Yang (Sustainable Cities and Society, 2026)

Preparation of plant-based meat analogues by soft matter method: Effects of NaCl concentrations and addition order - Jing-Wen Zhang; Qin Yang; Hui-Lin Li; Qing-Xuan Liu; Han-Qing Chen (Food Hydrocolloids, 2026)

A dual-function electroactive hydrogel platform for mitigating oxidative stress and restoring muscle function - Yi Lin; Zi-Hao Lin; Hai-Bin Jiang; Yu-Hao Kang; Qing-Song Deng; Rong-Tai Zuo; Zhi-Qi Lin; Er-Peng Yang; Jun-Jie Xu; Clara Chen; Xi-Ming Wang; Jin-Zhong Zhao (Chemical Engineering Journal, 2026)

Halorubrum marinum sp. nov., Halorubrum rarum sp. nov., Halorubrum wangae sp. nov., Halorubrum shenae sp. nov., and Halorubrum zhoui sp. nov., halophilic archaea from coastal tidal flats, a saline lake, and a marine solar saltern - Qing-Di Li; Yang-Yang Wang; Chidiebele Nwankwo; Yao Hu; Xin-Yue Dong; Jing Hou; Xiang-Dong Chen; Heng-Lin Cui (Systematic and Applied Microbiology, 2026)

Reducing carbon emission commitment constraints of Chinese passenger vehicle manufacturers through life cycle management - Keke Ji; Qing Yang; Zipeng Lin; Yuping Li; Xin Sun; Jiaxin Yu; Xingxing Liu; Liang Dong (Sustainable Production and Consumption, 2026)

Outdoor light at night exposure and hypertension risk in adults: A longitudinal cohort study from the FLORA project - Shuo Zhang; Xiao-Fan Lu; Muhammad Amjad; Lin-Jing Gong; Na Liu; Hong-Xing Zou; Xiao-Yi Liu; Le-Bing Wang; Yuan-Yuan Fan; Yang-Yang Li; Yi-Ran Chen; Wen-Wen Bao; et al. (Environmental Research, 2026)

Giant electrocaloric effect in bilayer BZT-BFO/Terpolymer nanocomposite films at a low electric field - Xiaodan Cao; Qing Qu; Dong Yang; Xin Zheng; Qinghang Zeng; Xiaoshi Qian; Zhong Lin Wang; Kailiang Ren (Chemical Engineering Journal, 2026)

Bio-etching regulated biomass coupled with nitrogen-enriched pyrolysis: A novel strategy for constructing high-nitrogen biochar and hydroxyacetonitrile-enriched bio-oil - Kunjie Chen; Bin Yan; Lin Zhu; Fan Yang; Qing Dong (Chemical Engineering Journal, 2026)

Single-enzyme-level hierarchical nanohybrids enable spontaneous electron relay, robust enzyme stability, and one-pot sensor printing - Qichao Pan; Yue Lu; Qing Wu; Qingui Yang; Xingyin Zhou; Qingsong Sun; Shouyan Zhang; Wei Wu; Shuhua Zhang; Zhi Geng; Xun Sun; Lin Jia; et al. (Chemical Engineering Journal, 2026)

Species Divergence in Oxytocin-Dependent Yawning on a Conserved Glutamatergic Erection Circuit - Yan-Chu-Fei Zhang; Qing-Wu Zheng; Yang Lu; Hao-Yuan Wang; Jiao Cang; Xin-Rui Wu; Lin-Yao Fan; Liang Li; Ni-Na Zhang; Xiao-Yang Zhang; Jing-Ning Zhu; Jian Jing; et al. (Neuroscience Bulletin, 2026)
Yawning coupled with penile erection is a conserved neurobehavioral syndrome mediated by the paraventricular hypothalamus (PVH). However, the distinct roles of oxytocin and its co-transmitters remain unresolved. Using chemogenetics, we showed that activation of PVH oxytocin neurons was sufficient to elicit both responses, whereas silencing these neurons abolished them. Viral tracing revealed that these neurons project collaterally to the brainstem reticular nucleus and spinal cord to spatially coordinate autonomic and somatic motor outputs. By dissecting the molecular mechanisms using CRISPR-Cas9, we found that vesicular glutamate transporter 2 (VGLUT2)-dependent glutamatergic transmission provides the primary drive for both behaviors, whereas the oxytocin peptide is selectively required for yawning but dispensable for erection. Comparative analyses across rats, hamsters, and mice demonstrated that while the glutamatergic erectile circuit was conserved, mice lacked spontaneous yawning and were resistant to apomorphine-induced yawning. These findings suggest a hierarchical co-transmission framework in which fast glutamatergic signaling provides the core drive, while oxytocin confers behavioral specificity.

Early and prolonged oral edaravone for neuroprotection in acute ischemic stroke: the ERASE-STROKE randomized controlled phase 3 trial - Yang Xiang; Wang-Sheng Jin; Xin-Chen Zhu; Yan Song; Xiao Chen; Qing-Hua Wang; Hao-Lun Sun; Yang Zhao; Xiao-Rong Yu; Tao Feng; Ai-Hong Guo; Hong-Guo Dai; et al. (Science Bulletin, 2026)

Minutes-long soft X-ray prompt emission from a compact object merger - An Li; Chen-Wei Wang; Niccolò Passaleva; Jie An; Bin-Bin Zhang; Eleonora Troja; Yi-Han Iris Yin; Yuan Liu; Shao-Lin Xiong; Li-Ping Xin; Yi-Xuan Shao; Jun Yang; et al. (Science Bulletin, 2026)

Cross-subject decoding of internal mental states using predictive time-series modeling - Zi-Han Wang; Xiao Chen; Bin Lu; Yu-Wei Wang; Xue-Ying Li; Hui-Xian Li; Yi-Fan Liao; Zheng-Jiayi Hu; Chen-Nan Wu; Han-Lin Wang; Qing-Lin Gao; Hai-Long Liu; et al. (Science Bulletin, 2026)

Particulate matter-bound metals and chlorinated paraffins co-exposure: A population-based study on attention-deficit/hyperactivity disorder in Chinese youth - Ya-Qin Zhang; Qi Yang; Hai-Xin Tu; Haseeb Tufail Moryani; Wan-Ting He; Jing-Wen Huang; Dan-Yao Zhou; Yun-Ting Zhang; Li-Xia Liang; Yang Zhou; Li-Zi Lin; Wen-Wen Bao; et al. (Journal of Hazardous Materials, 2026)

The undescribed alkaloids from Jacobaea cannabifolia (less.) E. Wiebe and their anti-inflammatory activities - Jian-Zhe Li; Juan Pan; Yu Bi; Zhi-Chao Hao; Wei Guan; Hai-Xue Kuang; Qing-Shan Chen; Li-Li Zhang; Xin-Yue Wu; Da-Lin Li; Bing-You Yang; Yan Liu (Natural Product Research, 2026)

Artificial Intelligence and Protein Design: A retrospective study on 20-year emerging trends and core research areas from bibliometric perspectives - Wenjuan Zhao; Xiuwu Pan; Wei Yang; Zichang Liu; Xiyi Wei; Anqi Lin; Bufu Tang; Lin Zhang; Mingjia Xiao; Qing Zeng; Quan Cheng; Weiming Mou; et al. (Probiotics and Antimicrobial Proteins, 2026)

Metric-dependent effects of microplastics on environmental antibiotic resistomes - Gengkui Huang; Shutong Lu; Baoshan Yang; Hui Wang; Qing-Lin Chen (Journal of Hazardous Materials, 2026)

Development and validation of a new derivatization-based quantitative analysis of multi-components by single marker strategy for simultaneous quantification of biogenic amines in fermented wine - Yue-Cai Hou; Xiao-Feng Huang; Ying Xue; Zhi-Xiang Yang; Lin-Sen Qing (Food Research International, 2026)

Co-exposure to polystyrene microplastics and Di-(2-ethylhexyl) phthalate exacerbates food allergy in mice associated with gut barrier dysfunction - Xuanpei Wang; Wenfeng Liang; Shiyun Chen; Ying Liu; Jiaxin Yu; Jianing Cui; Lin Xu; Min Fang; Zhiyong Gong; Xin Liu; Qing Yang (Food Bioscience, 2026)

A comprehensive review on the chemical composition, pharmacological effects and quality evaluation of Gentiana straminea Maxim. - Yuan-Wen Zhuang; Min Wang; Jian-Tao Zhao; Yu-Qing Wang; Run-Qian Yu; Huan Xia; Xiao-Hong Wei; Peng-Cheng Lin; Gui-Yang Xia; Sheng Lin (Journal of Natural Medicines, 2026)

Sustained Intra-Articular Delivery of Triple Therapeutics Using a Phase-Transition Phospholipid-Based Gel for Effective Treatment of Gouty Arthritis - Sirui Ma; Jing Yang; Ao Li; Qing Lin; Tao Gong (Pharmaceutical Research, 2026)

Fluorescence spectroscopy coupled with machine learning for identification of recycled PET - Ze-Long Deng; Qing-Hua Yang; Qi-Zhi Su; Xue-Chao Song; Qin-Bao Lin (Food Packaging and Shelf Life, 2026)

Single-cell sequencing reveals metabolic reprogramming and immune regulation underlie the maintenance of teleost granulomas - Zheng-Yang Zhou; Zheng-Ran Jian; Jin-Lai Gu; Xin-Yuan Jiang; Jie He; Yuan-Chang Gao; Sheng Lian; Shang-Jie Bai; Chen-Wang Lu; Lin-Feng Kuang; Ming-Zhu Liu; Peng-Fei Li; et al. (Fish & Shellfish Immunology, 2026)

From air to adipose: Investigating PM2.5-bound chlorinated paraffins and overweight/obesity in Chinese children and adolescents - Qi Yang; Hai-Xin Tu; Yu He; Ya-Qin Zhang; Muhammad Amjad; Jing-Fu Lai; Jing-Wen Huang; Yun-Ting Zhang; Wan-Ting He; Li-Xia Liang; Wen-Wen Bao; Yang Zhou; et al. (Environmental Research, 2026)

Lactiplantibacillus Plantarum O126 Postbiotics Boost growth, Antioxidant levels, Disease resistance, and Gut Health in Sea Cucumber (Apostichopus japonicus) - Feng-Li Chen; Hui-Ting Zhao; Wei Gu; Zong-Xiu Wu; Jing-Wen Xiang; Qing Yang; Yu-Lin Yang; Lei Tan; Meng-Xia Sun; Wei Cong; Shu Li; Bin-Tong Yang; et al. (Probiotics and Antimicrobial Proteins, 2026)

Shenrong Guben Huanshao Pill enhanced stress resistance and extended the lifespan of Caenorhabditis elegans by activating the oxidative stress system via the DAF-16/FOXO signaling pathway - Yi-Nan Yang; Xin Wang; Hong-Fen Jiang; Jie Yang; Subiy Akbara; Xiao-Qin Yang; Hai-Qing Fan; Guo-Lin Chai; Dong-Qing Fei; Fang-Di Hu; Shuang-Xi Qian; Zhan-Xin Zhang (Biogerontology, 2026)

Targeting perivascular adipose tissue in vascular aging: innovative translational strategies for disease prevention and monitoring - Peng-Xin Wang; Sha-Qi He; Bei Huang; Zi-Fei Liu; Feng Xu; Jun-Jie Yang; Sai Lu; Hui-Xiang Chen; Ze-Qiang Cai; Ling-Qing Yuan; Xiao Lin (Apoptosis, 2026)

Nanoimprinted topological laser in the visible - Qiang Zhang; Rui Duan; Yutian Ao; Lin Wang; Xuehong Zhou; Xuyong Yang; Qing Zhang; Xiao-Cong Yuan; Baile Zhang; Handong Sun (Science Bulletin, 2026)

Structurally diverse sesquiterpenoids from the fruits of Magnolia grandiflora Linn. and their cytotoxic activities - Qiu-Ye Zhao; Jin-Da Li; Shi-Huan Yin; Zhen-Quan Li; Hui-Ling Zhou; Jia-Qing Feng; Wei-Yang Feng; Xing-De Wu; Lin-Fen Ding (Phytochemistry, 2026)

MnO2-functionalized membrane with enhanced demulsification and antifouling performance for stable oil-in-water emulsion separation - Sudong Yang; Zhiying He; Mei Zhu; Junjie Zheng; Yixuan Kuang; Hongyi Li; Xueting Yuan; Qing Xu; Qian Zhang; Peng Zhao; Jianmin Luo; Lin Chen (Journal of Environmental Chemical Engineering, 2026)

Identification and validation of a QTL, QSNS.caas-3D.1, for spikelet number per spike in wheat - Xuezhong Liang; Junli Yang; Ze Liu; Fuping Zhang; Haiming Han; Shenghui Zhou; Jinpeng Zhang; Bing Han; Yida Lin; Hong-Qing Ling; Li Zheng; Junbo Yang; et al. (Theoretical and Applied Genetics, 2026)

Durability analysis of using MICP to address dispersive soil issues in seasonal freezing areas - Xiaoqing Yuan; Yuhui Wu; Cencen Niu; Xiaolong Yang; Sen Lin; Zeju Wu; Qing Wang; Hui’e Chen; Xin Xu; Hua Du (Soil and Tillage Research, 2026)

Lengthening vegetation carbon turnover time across China’s forests - Rong Ge; Xiaoli Ren; Honglin He; Guirui Yu; Li Zhang; Qian Xu; Mengyu Zhang; Shilong Piao; Kailiang Yu; Mathew Williams; Xiaobo Zhu; Shiyong Yu; et al. (Science Bulletin, 2026)

Multi-omics reveals efficient thiamethoxam biodegradation but altered flavor profile by native microbiota during Pixian broad bean paste fermentation - Xuan Yu; Siqi Huang; Jie Tang; Chuanning Peng; Qi Wen; Siqi Chen; Lanqi lei; Chenxi Yang; Yuanxi Liu; Wenliang Xiang; Qing Zhang; Hongbin Lin; et al. (International Journal of Food Microbiology, 2026)

Multi-stage study of pyrolysis kinetics, combustion characteristics, and fire modeling for selected nature wood species - Yi-Xuan Lin; Qiang Wang; Qi-Xian Li; Qing-Wen Lin; Peng-Rui Man; Shu-Nan Zhou; Yang Li; Jun Deng (Fuel, 2026)

Relationship of serum polycyclic aromatic hydrocarbon (PAHs) and lung function in adults: Evidence from a large community-based population in Guangzhou, China - Jing-Lin Zhang; Nuo Chen; Shui-Yue Lu; Michael S. Bloom; Shao Lin; Lu-Yin Wu; Li-Xia Liang; Yun-Ting Zhang; Jing-Wen Huang; Muhammad Amjad; Yong-Xiang Tang; Zhao-Huan Gui; et al. (Environmental Research, 2026)

Bone ECM-inspired gelatin methacryloyl/oxidized chitosan hydrogels with well-aligned fibrous structures guide stem cell alignment for restoring alveolar bone - Yangyang Lin; Caihao Huang; Qiang Wang; Haijiang Sun; Lei Cao; Yang Dong; Xue Meng; Xing Zhang; Lei Xue; Qing Zhou (Chemical Engineering Journal, 2026)

Polycyclic aromatic hydrocarbons-induced suppression of the PPARα/ACAA1 axis drives hepatic steatosis: Integrating epidemiology, network toxicology, and experimental validation - Haonan Cui; Peng Zou; Wang Yang; Shijun He; Jinyuan Shi; Ting Sun; Mengge Wang; Zhiyong Song; Hanni Guan; Tong Wang; Lei Sun; Qing Chen; et al. (Chemico-Biological Interactions, 2026)

Decoding microglial metabolic cell death and PANoptosis hub genes in subacute phase of traumatic brain injury: a multi-omics and experimental validation study - Zhe Wu; Bao-ya Yang; Jin-qing Lai; Shi-hong Lin; Long Lin; Jian-long Chen; Jia-xiang Pan; Yao-xin Ruan; Xiang-rong Chen (Apoptosis, 2026)

A New Species of Diaporthe Section Betulicola (Diaporthomycetidae, Diaporthales) From China - Yi Lan Jin; Xing Yu Luo; Kamran Habib; Yu Lin Ren; Qing Yang; Li Li Liu; Chanhom Loinheuang; Yang Chen; Qi Rui Li (New Zealand Journal of Botany, 2026)
A new species in Diaporthaceae, Diaporthe fengtaiensis sp. nov., is described and illustrated from Southwestern China. A comparative morpho‐anatomical study and multilocus phylogenetic analysis (ITS, CAL , HIS , TEF1‐α , TUB2 ) confirmed its position within the section Betulicola of the genus Diaporthe . The taxon is characterized by immersed ascomata (270–420 × 290–410 µm), relatively large asci (70–115 × 9.5–13.5 µm), and 1‐septate, fusiform ascospores (18.5–25.6 × 4.5–6.5 µm). Its positioning in a separate branch in the phylogenetic tree makes it distinct from the other known species of the section. A complete taxonomic treatment, based on two collected specimens, is provided along with molecular phylogenetic analyses.

The interplay between antihypertensive medication and lifestyle with cardiovascular outcomes in patients with hypertension: the PURE-China study - Biyan Wang; Zhiguang Liu; Tong Bu; Sumathy Rangarajan; Qiuyan Ma; Xiaocong Li; Qi Qiu; Yang Lin; Lap Ah Tse; Bo Hu; Salim Yusuf; Qiujing Cai; et al. (EPMA Journal, 2026)

A new sponge (Ascospongiae) from the early Cambrian Guanshan Biota - Lin-Jun Zou; Joseph P. Botting; Jie Yang; Xiao-Yu Yang; Wei Li; Qing-Hao Guo; Yu Wang; Chun-Li Li; Xi-Guang Zhang; Ai-Lin Chen (Palaeoworld, 2026)

Covalent modification of whey protein isolate by rosmarinic Acid: Impacts on physicochemical and functional properties - Qing Yang; Shiyun Chen; Xuanpei Wang; Yijie Chen; Lin Xu; Xiao Guo; Zhiyong Gong; Hao-Long Zeng; Xin Liu (Food Hydrocolloids, 2026)

Antibacterial properties and mechanisms of anti-lipopolysaccharide factor 1 from Procambarus clarkii - Qing Yang; Zhengyan Du; Lin Yang; Yujing Jia; Xinru Wang; Hao Li; Libo Hou; Lei Zhu; Xianghui Kong (Fish & Shellfish Immunology, 2026)

Biochar accelerated soil atrazine degradation by promoting dechlorination pathway: A novel mechanism revealed by DNA stable isotope probing (DNA-SIP) - Guiqiong Yang; Zhen Zhen; Kun Zhang; Junyong Yin; Xiaolan Zhong; Xiaofeng Li; Qing Li; Kaijiang Nie; Xiaoyang Miao; Zhong Lin; Dayi Zhang (Bioresource Technology, 2026)

Phytochemicals and health-promoting evaluations of Ophiorrhiza puffii , a chinese endemic plant - Qing Bu; Qi-Bin Yang; Zeng-Yue Ge; Ze-Xiong Shi; Lin-Fu Liang (Natural Product Research, 2026)

Discovery of FLF-15 as a novel selective inhibitor of ADAM17 to prevent hepatocellular carcinoma metastasis - Qing Li; Dao-ping Wang; Ting Zhong; Ai-ling Ling-hu; Jia-lin Chen; Fang Luo; Feng Zhang; Ming-zhi Su; Ying Yang; Yan-hua Fan (Molecular Diversity, 2026)

Lecithin supplementation to HFD improves largemouth bass liver health: Implications for regulating lipid homeostasis, antioxidant responses and endoplasmic reticulum stress - Biao Wang; Hua Zheng; Juan Xiong; Hong-Jun Yang; Qing-Lin Li; Zhi Luo (Fish Physiology and Biochemistry, 2026)

Warming-driven and depth-dependent responses of soil microbial communities toward nutrient limitations: Ecological insights into alpine grassland restoration - Hao Shi; Wei Wei; Jun-qiang Wang; Fei Xia; Cai-hong Yang; Lin-ling Ran; Yun-yin Xue; Hao-yang Wu; Shuang Yan; Yu Zhang; Shai-kun Zheng; Xiao-qing Qiu (Applied Soil Ecology, 2026)

Novel insights into cyanobacterial (microcystins) neurotoxicity in rats: hepatic encephalopathy - Wen-Li Xu; Liang Chen; Hui-Hui Fan; Geoffrey A. Codd; John P. Giesy; Yu-Ming Guo; Elizabeth D. Hilborn; Daniela Sedan; Darío Andrinolo; Saurabh Chatterjee; Hai-Jun Wang; Ying Liu; et al. (Archives of Toxicology, 2026)

Analysis of antimicrobial resistance and virulence of Vibrio parahaemolyticus - Zhu-qing Shen; Xiao-lin Zhang; Yu-qing Zhou; Meng-hua Yang; Yu-bin Su; Bo Peng (Marine Pollution Bulletin, 2026)

Single-cell RNA sequencing reveals the immune cell landscape of head kidney in the Perciform fish (Micropterus salmoides) - Zheng-Yang Zhou; Chen-Wang Lu; Zheng-Ran Jian; Shang-Jie Bai; Lin-Feng Kuang; Jin-Lai Gu; Ming-Zhu Liu; Peng-Fei Li; Gao-Xue Wang; Qing Yu; Fei Ling; Jorge Galindo-Villegas; et al. (Aquaculture, 2026)

Interface states of surface water waves based on Fibonacci corrugations with mirror symmetry - Qing-Dong Hong; Lei Yang; Rui-Lin Liu; Shu-Ya Jin; Ya-Xian Fan; Zhi-Yong Tao (Wave Motion, 2026)

Long-term ozone exposure and attention-deficit/hyperactivity disorder symptoms in school-aged children: Findings from a large multi-city study in China - Zhao-Huan Gui; Wan-Ting He; Yun-Ting Zhang; Joachim Heinrich; Michael S. Bloom; Shao Lin; Bin Jalaludin; Mohammed Zeeshan; Lidia Morawska; Tian-Yu Zhao; Shyamali Dharmage; Luke Knibbs; et al. (Journal of Hazardous Materials, 2026)

Electrochemical detection and electro-Fenton degradation of fipronil via Fe/Ni-BTC/MS-derived NiFe2O4@C core-shell catalyst - Yu-Qing Zhan; Cheng-Guo Liu; Jia-Jia Kou; Yi-Lin Niu; Hai-Jiao Xie; Liu Yang; Dashu Chen (Journal of Cleaner Production, 2026)

Unveiling the metabolic mechanism of pesticide in food fermentation through metagenomics and metabolomics: A case study of β-cypermethrin in Pixian broad-bean paste - Siqi Huang; Xuan Yu; Jie Tang; Chuanning Peng; Qi Wen; Siqi Chen; Lanqi lei; Chenxi Yang; Yuanxi Liu; Wenliang Xiang; Qing Zhang; Hongbin Lin; et al. (Food Chemistry, 2026)

Associations of particulate matter size fractions and chemical composition with conjunctivitis and eczema: epidemiological evidence from the Pearl River Delta, China - Lu-Yin Wu; Mohammed Zeeshan; Yun-Ting Zhang; Li-Xia Liang; Jing-Wen Huang; Wen-Wen Bao; Yang Zhou; Muhammad Amjad; Li-Zi Lin; Ru-Qing Liu; Zhi Wang; Guang-Hui Dong (Environmental Research, 2026)

Exploring the Role of B-Cell Biotherapy in Myasthenia Gravis from a Genetic Perspective: A Mendelian Randomization Study - Mengyuan Zhang; Cen Yue; Jie Fang; Jiahui Tang; Caihong Chen; Caili Zhou; Wanli Yang; Xingkai An; Qing Lin; Jiawei Zhang (Molecular Neurobiology, 2026)

Performance of blood biomarkers in internal jugular vein for Alzheimer’s disease pathologies: the Delta Method study - Jun Wang; Dong-Yu Fan; Shan Huang; Chang Liu; Pei-Wen Zhao; Nan Wu; Xiao-Lin Gao; Qing-Zhi Wang; Yanli Li; Bai Liu; Yuan-Ye Ma; Rong-Chang Zhao; et al. (Science Bulletin, 2025)

Influence of planting patterns on Ligusticum sinense cv. Chuanxiong development and its rhizosphere microenvironment - Lin Liu; Ting Li; Hao-ran Song; Xiu-wen Bao; Jia Ye; Qing-he Wang; Jing Bai; Si-jing Liu; Yang Li; Shu-qi Niu; Jin-lin Guo (Journal of Cleaner Production, 2025)

Three tetraspanins, Tspan1, Tspan2A and Tspan3 from Litopenaeus vannamei involved into Vibrio parahaemolyticus infection - Yi-Qian Zhang; Shuang-Shuang Luo; Xiu-Li Chen; Ai-Jin Wang; Chao-Jie Hou; Qing-Yun Liu; Min Peng; Chun-Ling Yang; Yan Lei; Wei-Lin Zhu; Hong Liu; Yong-Zhen Zhao; et al. (Fish & Shellfish Immunology, 2025)

MOF-derived core-shell MnFe2O4@C bifunctional material: Electrochemical sensing and synergistic electro-Fenton degradation of clothianidin - Jia-Jia Kou; Yu-Qing Zhan; Yi-Lin Niu; Hai-Jiao Xie; Liu Yang; Dashu Chen (Chemical Engineering Journal, 2025)

Homogeneous MgF2-engineered Na surface architecture enabling uniform ion deposition in ultra-stable sodium metal batteries - Xueming Su; Junjie Fu; Lin Luo; Xiaoquan Yang; Yue Li; Weijiang Hu; Qing Li; Qingye Li; Chencheng Sun; Jun Yang; Hongwei Gu (Chemical Engineering Journal, 2025)

A pH-responsive and nitric oxide-producing nanocarrier for targeted therapy of melanoma - Shuai Cui; Qing Yu; Ziyuan Su; Yiting Han; Sujuan Wang; Xiangyu Zou; Lin An; Nannan Yin; Hao Hong; Dongzhi Yang (Chemical Engineering Journal, 2025)

Decades’ progress and prospects on maize functional genomics and molecular breeding - Qing Li; Jinsheng Lai; Jian Chen; Lin Li; Weibin Song; Beibei Xin; Hainan Zhao; Yingjie Xiao; Feng Tian; Gang Li; Yameng Liang; Lei Liu; et al. (Science China Life Sciences, 2025)

Voltage-Gated sodium channel Nav1.6 mediates glioblastoma proliferation and migration via Na+/H+ Exchanger-1 and inhibits apoptosis through ERK-AKT pathway - Samed Ahmed Alezzi Alameri; Yue Kong; Qing-Da Shi; Yue-Lin Huang; Ao-Ran Sui; Dan-Dan Zhu; Ying-Zi Wang; Wang Miao; Shao Li; Guang Yang (Molecular Biology Reports, 2025)

Effects of phenological uniformity on prediction accuracy of wheat yield and biomass - Yandong Yang; Qing Li; Qinwen Lin; Huimin Wang; Yi Shi; Gengchen Wu; Yue Mu; Dong Jiang; Seishi Ninomiya (Field Crops Research, 2025)

Mucus cell-inspired microstructure lubricative gel surface: Secretory, trap-locked and dual antithrombotic - Jun Zhong; Qing Yang; Xiaodan Gou; Mengchen Xu; Qingyun Ma; Lin Kai; Haoyu Li; Mingyong Luo; Feng Chen (Chemical Engineering Journal, 2025)

Seasonal variations of amines in PM2.5 in a coastal city of southeastern China: Formation mechanisms and sources - Naihua Chen; Qing Lin; Yuerong Wu; Jianyong You; Yuxiang Yang; Limei Zhang; Zhiwei Zeng; Yue Gao; Jinfeng Zeng; Baoye Hu (Atmospheric Environment, 2025)

The dietary supplementation with probiotic Bacillus cereus G1-11 improved the growth parameters, immune performances, intestinal histomorphology, and disease resistance of hybrid grouper (Epinephelus fuscoguttatus ♀ × Epinephelus lanceolatus ♂) - Ming-Qing Zhang; Zhong-Xuan Zhong; Qian-Ping Du; Wen Li; Ya-Ting Zhu; Guang-Ting Xie; Feng-Ying Yan; Jin-Lin Yang; Shui-Sheng Li; Hu Shu (Animal Feed Science and Technology, 2025)

Transferrin receptor 1 is an entry factor for Japanese encephalitis virus - Qing Yang; Shengda Xie; Yundi Zhao; Xinxin Lin; Ning Wei; Miaolei Shi; Ruibing Cao (Veterinary Microbiology, 2025)

Separation and recovery of iron from vanadium extraction tailing slag by P204-P507 mixture collector flotation process - Yi-bo Wang; Jing-wei Li; Xiao-long Liu; Xin-fei Jiang; Yin-he Lin; Zhi Tian; Jun-jie Yin; Bing-qing Huang; Jia-xin Yang; Chen-xuan Wang; Zi-wang Wu; Shi-xing Ma; et al. (Journal of Environmental Chemical Engineering, 2025)

Multi-channel thermal conductive phosphor-in-glass film with a record laser power density threshold for laser lighting - Hao Cheng; Yang Wang; Jiuzhou Zhao; Qing Wang; Shisheng Lin; Jiaxin Liu; Yun Mou; Lei Nie; Mingxiang Chen; Zhen Zhang; Yang Peng; Daqin Chen (Chemical Engineering Journal, 2025)

A novel approach for wave-turbulence decomposition - Jianliang Lin; Chunyan Zhu; Jianwei Sun; Weiming Xie; Bram van Prooijen; Leicheng Guo; Qing He; Qingshu Yang; Zheng Bing Wang (Coastal Engineering, 2025)

Senegenin ameliorates diabetic encephalopathy via promoting mitophagy and repressing NLRP3 inflammasome activation - Xiao-dan Yan; Yu Yang; Wan-ting Zhang; Qing-quan Kong; Xi-tong Zheng; Lin-sen Li; Qing Yu (Psychopharmacology, 2025)

Deinococcus lichenicola sp. nov., A Bacterium Isolated from a Lichen Sample - Guo-Hua Chen; Lian-Shuang Xiong; Rui Yang; Shu-Ya Zuo; Qing Yuan; Li-Song Wang; Cheng-Lin Jiang; Xin-Yu Wang; Yi Jiang (Current Microbiology, 2025)

Dual-signal enhanced lateral flow immunoassay with nanobody-functionalized magnetofluorescent nanoprobes for multiplexed detection of foodborne pathogens - Wenjin Hu; Shengyang Wang; Qing Du; Shixiang Yang; Xiaxia Wei; Xi Li; Huai Lin (Analytica Chimica Acta, 2025)

Chemotaxonomically significant phytochemicals with α-glucosidase and tyrosinase inhibitory activities from Chinese endemic plant Ophiorrhiza hunanica - Qing Bu; Qi-Bin Yang; Can-Qi Liu; Zeng-Yue Ge; Xiao-Wen Liao; Lei Wu; Lin-Fu Liang (Natural Product Research, 2025)

Geological Structural Characteristics of Subashi in West Kunlun Revealed by Aero Geophysical and Remote Sensing Data - Ming Wang; Yi-chuan Li; Hai-qing Wang; Yan-yan Wei; Xiao-xing Lin; Dao-qing Zhou; Jin-zhong Yang; Chang Zhong; Chang-chun Yu (Applied Geophysics, 2025)

First experiment using post-accelerated unstable ion beams at BRIF: angular distribution of the 21 , 22 Na elastic scattering from doubly magic 40 Ca - Wei Nan; Bing Guo; Cheng-Jian Lin; Dan-Yang Pang; Lei Yang; Dong-Xi Wang; Guo Yang; Yang-Ping Shen; Bing Tang; Qi-Wen Fan; Yi-Wen Bao; Lei Cao; et al. (Science Bulletin, 2025)

Seven previously undescribed steroidal alkaloids from the fruit of Solanum nigrum L. and their biological activities - Liang-Yu Liu; Qing Peng; Yu-Ke Yang; Tong Wu; Li-Xian Chen; Li Lin (Phytochemistry, 2025)

Using ventilation hood during cooking reduced household air pollution exposure and brought cardiometabolic and pulmonary health benefits: A community-based, cluster-randomized controlled intervention study - Yueru Yang; Kuai Yu; Wending Li; Xuedan Xu; Chengyong Jia; Qi Yan; Xingxing Li; Hao Cai; Denghuan Hu; Hui Gao; Xuanwen Mu; Yuhui Lin; et al. (Journal of Hazardous Materials, 2025)

Tremella fuciformis Polysaccharides Alleviate Early Brain Injury in Experimental Subarachnoid Hemorrhage by Inhibiting the KDR-Mediated P38 MAPK/NF-κB Pathway - Yu-hui Wan; Zeng-jing Cheng; Ling-xiang Fan; De-hong Yang; Bing-lin Chen; Xiang-xin Chen; Qing Zhu (Molecular Neurobiology, 2025)

Whole-genome resequencing-based assessment of genomic diversity and selection signatures in Rhipicephalus microplus from Shaanxi, China - Yi-yao Mou; FU-wen Wang; YU-kun Kang; Ya-qing Li; YU-ying Yang; Tian-yuan Liu; Chu-zhao Lei; Qing Lin (Veterinary Parasitology, 2025)

Chinese Tuina ameliorates muscle damage by regulating endoplasmic reticulum stress and autophagy in a rat model of skeletal muscle contusion - Hai-chao Liu; Hao-ming Zhu; Ming Li; Bo-rui Chen; Zheng-yu Yang; Yu Wang; Shi-zhong Wang; Shao-qing Chen; Jian-ping Lin (Tissue and Cell, 2025)

Subgenual anterior cingulate cortex functional connectivity abnormalities in depression: insights from brain imaging big data and precision-guided personalized intervention via transcranial magnetic stimulation - Xiao Chen; Bin Lu; Yu-Wei Wang; Xue-Ying Li; Zi-Han Wang; Hui-Xian Li; Yi-Fan Liao; Daniel M. Blumberger; Francisco Xavier Castellanos; Eduardo A. Garza-Villarreal; Li-Ping Cao; Guan-Mao Chen; et al. (Science Bulletin, 2025)

Gold-catalyzed construction of atomically rough surfaces towards high-efficiency ethanol electrooxidation - Qing Zeng; Mengyuan Ma; Hui Liu; Lin Xu; Shaonan Tian; Dong Chen; Jing Wang; Jun Yang (Science Bulletin, 2025)

Experimental investigation of hydroelastic response and resonance characteristics in anaconda wave energy converter - Yang Huang; Qing Xiao; Saishuai Dai; Lin Cui; Liu Yang; Saeid Lotfian; Farhad Abad; Guillermo Idarraga; Feargal Brennan (Ocean Engineering, 2025)

Incidence of respiratory diseases associated with per- and polyfluoroalkyl substances (PFAS) in PM2.5: New evidence from a population-based survey of Pearl River Delta (PRD), China - Lu-Yin Wu; Wan-Ting He; Mohammed Zeeshan; Yang Zhou; Yun-Ting Zhang; Li-Xia Liang; Jing-Wen Huang; Jia-Xin Zhou; Kun Zhao; Wen-Wen Bao; Li-Zi Lin; Zhao-Huan Gui; et al. (Journal of Hazardous Materials, 2025)

The influence of water-soluble arabinoxylan on the rheological properties of model dough and the interfacial properties of imitation dough liquor - Tongtong Zhou; Yucong Zhang; Shiming Zhou; Qing Liu; Qianzhu Lin; Yihui Wang; Yueyue Yang; Chao Qiu; Aiquan Jiao; Zhengyu Jin (Food Chemistry, 2025)

Generating three-dimensional soil organic carbon density dataset by soil depth function and correction methods in Yangtze River Delta, China - Shurui Lin; Qing Zhu; Beini Yin; Guishan Yang; Kaihua Liao; Xiaoming Lai; Changqiang Guo (Environmental Modelling & Software, 2025)

Manipulating π electron behavior of graphene for remarkable solar steam generation and salt recovery - Qiang Tang; Yi-Le Chen; Jia-Wei Zhu; Huan Jin; Ming Xue; Lin Gu; Jing Yang; Qing-Yun Wu (Desalination, 2025)

Revolutionary photoelectrochemical water splitting performance of BiVO₄/Bi₂S₃ heterojunction photoanodes boosted by trace bio-Cr₂O₃ through multiple mechanisms - Yefei Su; Yang Yu; Tingting Xue; Kai Teng; Yuning Fan; Jiangjun Lin; Chang Liu; Qing Qu; Lei Li (Chemical Engineering Journal, 2025)

Effect of cadmium-resistant Proteus mirabilis Ch8 on active ingredients and cadmium content of traditional Chinese medicine Ligusticum sinense cv. Chuanxiong - Ting Li; Lin Liu; Xiu-wen Bao; Fei-fei Liu; Xuan Zhang; Hao-ran Song; Si-jing Liu; Jing Bai; Qing-he Wang; Fei-lin Yang; Yang Li; Shu-qi Niu; et al. (Plant and Soil, 2025)

The Association of Blood Cobalt Levels with Cardiovascular and Chronic Kidney Diseases: Mediating Role of Inflammatory Indicators (SII, NLR, PLR, NMLR, and LMR) - Bei-Bei Lu; Qian Luo; Xiao-Lin Yuan; Qing-Song Chen; Jing-Yang Ran; Xing-Wei Zhe; Xiao-Hui Liao (Cardiovascular Toxicology, 2025)

A new phenolic compound from Persicaria capitata - Lei He; Fei Zhong; Xing-Jun Chen; Ya-Ru Yang; Xue-Long Yan; Ming-Hui He; Xu Zhang; Mu-Zhen Wang; Yong-Qin Zeng; Qin-Feng Zhu; Zhu Zeng; Bo Tu; et al. (Natural Product Research, 2025)

Viscosity is a nonnegligible factor in the waste activated sludge fermentation: Taking hyaluronan as an example - Yan-Lin Hu; Kun Dai; Qing-Ting Wang; Chen-Yuan Zhou; Xing-Chen Huang; Xiao-Fei Yang; He-Liang Pang; Raymond Jianxiong Zeng; Fang Zhang (Water Research, 2025)

Transfer patterns of human blood to follicular fluid of per- and polyfluoroalkyl substances with distinct molecular structures and physico-chemical properties - Yun-Ting Zhang; Michael S. Bloom; Yang Zhou; Saif Ur Rehman; Chu Chu; Kun Zhao; Biao Yin; Zhong Lin; Yuan-Yuan Fan; Li-Zi Lin; Ru-Qing Liu; Weihong Tan; et al. (Journal of Hazardous Materials, 2025)

Quantifying regional transport contributions to PM2.5-bound trace elements in a southeast coastal island of China: Insights from a machine learning approach - Naihua Chen; Jianyong You; Qing Lin; Limei Zhang; Zhiwei Zeng; Yue Gao; Jinfeng Zeng; Baoye Hu; Yuxiang Yang (Environmental Pollution, 2025)

N,O-interlocked cavity-structured functionalized metal–organic frameworks for one-step efficient removal of highly toxic thorium from tailings wastewater - An-Min Song; Zhi Wu; Bin Lin; Meng-Jie Yang; Qing Yang; Shu-Yuan Zhang; Xiao-Xing Wang; Zhi-Hai Peng; Ru-Ping Liang; Jian-Ding Qiu (Chemical Engineering Journal, 2025)

Tunable containing malononitrile AIEgens with reversible mechanochromic behaviors and promising applications - Guang Yang; Wen-Xuan Zhao; Ling Liang; Zeng-Min Xue; Fei Meng; Yu-Qing Kong; Hong-Tao Lin; Shu-Hai Chen; Chuan-Zeng Wang (Chemical Engineering Journal, 2025)

Airborne Microplastic Pollution in a Highly Urbanized City: Occurrence, Characteristics, Human Exposure and Potential Risks - Yijing Gan; Xinlu Yang; Lixiang Zhong; Xinyan Chen; Mingfu Lin; Xian Qing; Laiguo Chen; Jun Wang; Yumei Huang (Water, Air, & Soil Pollution, 2025)

Geological model for the fault electric field and its significance for earthquake prediction - Zhen Chen; Zhanhui Qing; Xiaodong Yang; Xiaoming Lin; Guoneng Chen (Natural Hazards, 2025)

Deepening and narrowing impacts on circulation, stratification, and sediment transport in the Changjiang Estuary - Jianliang Lin; Bram C. van Prooijen; Chunyan Zhu; Leicheng Guo; Qing He; Zheng Bing Wang; Qingshu Yang (Frontiers in Marine Science, 2025)
Channel deepening and narrowing are common anthropogenic modifications in estuaries, but their combined effects on estuarine circulation, stratification, and sediment transport remain insufficiently understood. This study investigates these combined impacts in the North Passage of the Changjiang Estuary, where large-scale deepening and narrowing have significantly altered hydrodynamic and sediment processes. Our analysis demonstrates that channel deepening intensifies estuarine circulation by strengthening the landward near-bed flow, thereby enhancing sediment import. Contrary to initial expectations that narrowing would promote sediment flushing, our results indicate that narrowing increases stratification, steepens along-estuary salinity gradients, and suppresses vertical mixing. Intensified stratification further reinforces estuarine circulation, promoting sediment trapping at the saltwater intrusion limit. Additionally, enhanced tidal pumping driven by increased velocity and suspended sediment concentration gradients extends the estuarine turbidity maximum both upstream and downstream, a process often overlooked in engineered estuaries. These findings challenge conventional assumptions regarding the sedimentary impacts of narrowing, emphasizing instead its critical role in amplifying estuarine circulation and sediment trapping. Our results provide new insights into sediment dynamics in river-dominated estuaries, with significant implications for estuarine management, dredging operations, water quality control, and long-term morphological stability.

A Novel Metric for Assessing Long-Term Outcomes in Adults with Chiari Malformation Type I: Occipitocervical Dura Angulation (ODA)—Applications and Value - Bo Wang; Shi-Chao Chen; Yao-Wu Zhang; Wei-Hao Liu; Chong Wang; Yi-Xiang Liu; Guang-Hao Zheng; Jia-Lin Li; Kai Ji; Jun Yang; Yong-Zhi Wang; Wen-Qing Jia (The Cerebellum, 2025)

Whole-genome sequences revealed genomic diversity and selection signatures of Dermacentor silvarum in Shaanxi, China - Yi-yao Mou; Meng-ke Lin; Yu-ying Yang; Yu-kun Kang; Ya-qing Li; Tian-yuan Liu; Chu-zhao Lei; Qing Lin (Veterinary Parasitology, 2025)

Potential viral influence on sulfur metabolism in acid sulfate soils - Li Bi; Shuai Du; Rob Fitzpatrick; Qing-Lin Chen; Thi Bao-Anh Nguyen; Zi-Yang He; Ji-Zheng He; Hang-Wei Hu (Soil Biology and Biochemistry, 2025)

Searching for neutrinoless double-beta decay of 136 Xe with PandaX-4T - Shu Zhang; Zihao Bo; Wei Chen; Xun Chen; Yunhua Chen; Zhaokan Cheng; Xiangyi Cui; Yingjie Fan; Deqing Fang; Zhixing Gao; Lisheng Geng; Karl Giboni; et al. (Science Bulletin, 2025)

Three new sesquiterpenes with cytotoxic activity from Croton tiglium - Wen-Ying Zhou; Xiao-Xiao Zheng; Yang-Mei Ou; Yang-Lin Ou; Hong-Yu Jang; Yu-Xin Peng; Yi-Yi Wang; Bi-Qing Zhao; Li Li (Phytochemistry Letters, 2025)

Spring festival firework activities exacerbate toxic effects of aerosol essential components - Uudam Hu; Ying Sun; Guoqing Yang; Mingqi Liu; Yue Gao; Liu Lin; Yingnan Cao; Wei Liu; Yaoqiang Huo; Jianguo Liu; Qing Li (Journal of Hazardous Materials, 2025)

Phenol-driven ammonium recovery from coal chemical wastewater in a bioelectrochemical system (BES) - Ran Zeng; Li-Hui Yang; Si-Yuan Zhai; Cheng-Yan Liu; Na Lin; Qing-Hua Ou-Yang; Yan-Hua Xu; Ai-Jie Wang; Hao-Yi Cheng (Journal of Hazardous Materials, 2025)

Climate suitability determines optimal yielding of dryland maize: A validation on timely sowing as an ancient wisdom - Jing Wang; Ling Zhao; Meng Hao; Ning Wang; Qing-Hui Wen; Fu-Jian Mei; Aziz Khan; Bao-Zhong Wang; Xiao-Lin Zhang; Wei Wang; Chang-Lang Yang; Fei Mo; et al. (Field Crops Research, 2025)

Epigenetics in the modern era of crop improvements - Yan Xue; Xiaofeng Cao; Xiangsong Chen; Xian Deng; Xing Wang Deng; Yong Ding; Aiwu Dong; Cheng-Guo Duan; Xiaofeng Fang; Lei Gong; Zhizhong Gong; Xiaofeng Gu; et al. (Science China Life Sciences, 2025)
Epigenetic mechanisms are integral to plant growth, development, and adaptation to environmental stimuli. Over the past two decades, our comprehension of these complex regulatory processes has expanded remarkably, producing a substantial body of knowledge on both locus-specific mechanisms and genome-wide regulatory patterns. Studies initially grounded in the model plant Arabidopsis have been broadened to encompass a diverse array of crop species, revealing the multifaceted roles of epigenetics in physiological and agronomic traits. With recent technological advancements, epigenetic regulations at the single-cell level and at the large-scale population level are emerging as new focuses. This review offers an in-depth synthesis of the diverse epigenetic regulations, detailing the catalytic machinery and regulatory functions. It delves into the intricate interplay among various epigenetic elements and their collective influence on the modulation of crop traits. Furthermore, it examines recent breakthroughs in technologies for epigenetic modifications and their integration into strategies for crop improvement. The review underscores the transformative potential of epigenetic strategies in bolstering crop performance, advocating for the development of efficient tools to fully exploit the agricultural benefits of epigenetic insights.

miR-758-3p Interferes with Neuronal Apoptosis in Cerebral Ischemia–Reperfusion by Inhibiting ILK - Xiaoli Min; Xuesong Bai; Qing Zhao; Wenwu Yang; Sixian Lin; Lei Xian; Rui Jing; Xuhui Li; Wenji Jia; Wei Miao; Mei Yin; Feifei Shang; et al. (Molecular Neurobiology, 2025)

Cost-effective production of squalene using Yarrowia lipolytica via metabolic engineering and fermentation engineering - Wen-Bo Lin; Hong Chen; Ze-Qi Song; Yu-Qing Pan; Peng-Cheng Hu; Xiao-Na Yang; Xiang-Yang Lu; Yun Tian; Hu-Hu Liu (Biotechnology Letters, 2025)

COP1 Overexpression Attenuates Nociceptive Behaviors and Neuroinflammation in Cancer-Induced Bone Pain by Suppressing c/EBPβ - Dan-Yang Li; Lin Liu; Shao-Jie Gao; Dai-Qiang Liu; Long-Qing Zhang; Jia-Yi Wu; Fan-He Song; Xin-Yi Dai; Ya-Qun Zhou; Wei Mei (Journal of Neuroimmune Pharmacology, 2025)

Low-level exposure to environmental lithium element affects male reproductive outcomes: Results from the MARHCS cohort study in Chongqing, China and in vivo animal experiments - Lihong Wang; Guanghui Zhang; Xi Ling; Mei Wan; Qing Chen; Lei Sun; Huan Yang; Tong Wang; Jinyi Liu; Jia Cao; Lin Ao; Peng Zou (Reproductive Toxicology, 2025)

Collagenases from hepatopancreas and muscle of Litopenaeus vannamei: Purification, characterization and comparison of their behaviors in collagen degradation - Xu-Chen Xiao; Jia-Yin Huang; Yu-Lei Chen; Kai-Yuan Cao; Ru-Qing Yang; Duan-Quan Lin; Shu-Jun Hong; Yu-Ting Yang; Min-Jie Cao (Food Chemistry, 2025)

Soil viruses regulate soil nutrient cycling through themselves and their effects on host functioning to impede the growth of continuously planted Casuarina equisetifolia - Yu-Hua Wang; Lei Hong; Yi Lin; Miao-En Qiu; Jian-Juan Li; Qing-Xu Zhang; Xiao-Li Jia; Yu-Lin Wang; Li-Yuan Wang; Yang-Xin Luo; Wen-Xiong Lin; Hai-Bin Wang; et al. (Applied Soil Ecology, 2025)

Toxicity of rare earth elements europium and samarium on zebrafish development and locomotor performance - Boyu Yang; Luning Sun; Zheng Peng; Qing Zhang; Mei Lin; Zhilin Peng; Jue Yang; Lan Zheng (Journal of Hazardous Materials, 2025)

The enhancement of extracellular electron transfer processes through the design of biomimetic grape-like materials - Yao Meng; Xu Pan; Ye Chen; Qing Wen; Cunguo Lin; Haiping Gao; Zhenghui Qiu; Liuqingying Yang (Journal of Environmental Chemical Engineering, 2025)

2-Mercapto-1,3,4-thiadiazole-functionalized gold nanoclusters as a comparable bactericidal nanoantibiotic to vancomycin in treating methicillin-resistant Staphylococcus aureus infections - Quan-Quan Zhuang; Jia-Xin Ma; Yi-Ming Zheng; Lin-Yan Lu; Jia-Lin Yang; Qing-Qing Chen; Xiao-Li Yan; Yan-Cheng Jiang; Hao-Hua Deng; Wei Chen; Gang Liu (Chemical Engineering Journal, 2025)

Long-term organic farming improves the red soil quality and microbial diversity in subtropics - Yongkang Wen; Wei Yao; Taobing Yu; Lang Cheng; Qing Zhang; Jida Yang; Fangding Lin; Hongye Zhu; Anna Gunina; Yadong Yang; Kevin Z. Mganga; Zhaohai Zeng; et al. (Agriculture, Ecosystems & Environment, 2025)

Extraction, rapid preparation and neuroprotective effect of texasin, a main active constituent from Caragana jubata (Pall.) Poir. - Zi-Yang Xu; Qi-Jun Dai; Yu-Fan Huang; Bo-Lin Zou; Xin Lu; Jian-Bin Wang; Han-Qing Pang; Wen-Jun Xu; Liang Liu (Natural Product Research, 2025)

Exploration of the regulatory mechanism of pulsed electric field on the aggregation behavior of soybean protein isolates - Rui Wang; Pei-Feng Guo; Jin-Peng Yang; Yan-Yan Huang; Lang-Hong Wang; Jian Li; Song-Yi Lin; Qing-Lin Sheng; Xin-An Zeng; Yong-Xin Teng (Food Hydrocolloids, 2025)

Research on improving the quality of groundwater self-monitoring via Blockchain technology - Haixiang Li; Dongxue Fu; Meiyue Yang; Sijie Lin; Song Zongzhong; Wei Jiang Liu; Qing Hu (Environmental Impact Assessment Review, 2025)

Terrestrial ecosystem response to Early Cretaceous global environmental change: A calibrated, high-resolution Aptian record from Northeast China - Ming-Dao Sun; Qin Lin; Jahandar Ramezani; Jiang-Si Liu; Zheng-An Lu; Han-Qing Yang; Jiang-Hao Bai; Shi-Xi Cai; Jun-Cai Chen; Xuan-Yu Chen; Hao Cui; Guang-Chao Deng; et al. (Earth and Planetary Science Letters, 2025)

High-speed atomic force microscopy reveals opposite traffic of processive chitinases impairs α-chitin biodegradation - Mingbo Qu; Lin Kong; Pengfei Li; Aijing Zhang; Toshio Ando; Qing Yang (Carbohydrate Polymers, 2025)

Heterogeneous Fenton-like catalysts of tetranitro iron phthalocyanine@Fe3O4@fly ash composites for fast decomposition of environmental contaminants - Dapeng Li; Peng Zhang; Yang Jin; Qing Li; Xinyuan Li; Ruirui Chang; Ruoxi Ma; Lin Yan; Suxiang Ge; Juntao Ma (Waste Disposal & Sustainable Energy, 2025)
Using fly ash (FA) solid wastes as economical carriers to construct Fenton-like catalytic composites with additional functions is more practical than the use of a single catalyst. Understanding the structure and properties of catalysts and carriers is vital to improve performance. Tetranitro iron phthalocyanine (TNFePc) is a highly active molecular catalyst, whose immobilization and Fenton-like heterogeneous catalysis remain unclear. In this study, magnetically recyclable composites of TNFePc@Fe 3 O 4 @FA were successfully fabricated. Further, Fe 3 O 4 nanocrystals decorated on FA surfaces could be used as special functional layer for composite recycling and simultaneous in situ TNFePc synthesis. Peroxides of H 2 O 2 , KHSO 5 , and tert-butyl hydrogen could be effectively activated by composites and transformed into highly reactive radicals. Moreover, molecular oxygen could be activated as well. Model pollutants, methylene blue and oxytetracycline, could be synergistically degraded by the radical oxidation of superoxide, hydroxyl, alkoxy, and sulfate radicals and non-radical oxidation of high-valent iron-oxo species of TNPcFe IV =O. To the best of our knowledge, this is the first design of FA-based composites with dual function, Fenton-like heterogeneous catalysis and magnetic recyclability, for environmental decontamination. Graphical abstract

MRI Shrimp Sign and Parietooccipital Lesion in Progressive Multifocal Leukoencephalopathy - Wen-Qian Luo; Bin Liu; Chun-Lin Yang; Ze-Yu Zhao; Guan-Qing Wang; Xiao-Li Li; Peng Zhang (The Cerebellum, 2025)

Transportation development paths in 30 provinces of China in the context of carbon quota allocation - Keke Ji; Qing Yang; Liang Dong; Zipeng Lin; Kaili Ji; Ting Zhang; Xingxing Liu (Journal of Transport Geography, 2025)

Trimeric tetrapeptide repeat protein TPR16 positively regulates salt stress in apple - Qing Wang; Da-Ru Wang; Xin Liu; Guo-Lin Chen; He-Dan Li; Wen-Long Ji; Man-Shu Qu; Rui Yang; Chun-Xiang You (Journal of Plant Physiology, 2025)

Synergistic effect of bimetallic bioelectrocatalysis and endogenous soluble electron mediators for functional regulation of electroactive biofilms - Xu Pan; Ye Chen; Qing Wen; Cunguo Lin; Haiping Gao; Zhenghui Qiu; Liuqingying Yang (Journal of Cleaner Production, 2025)

A systematic comparative analysis of ginger-related varieties from three dimensions based on HS-SPME-GC-Q-TOF MS and UHPLC-LTQ-Orbitrap MS - Huan-ya Yang; Lin Yang; Yu-lu Wang; Yun-shu Hu; Yun Li; Hua Qu; Wen-long Wei; Hui-yan Yang; Qi-rui Bi; Jian-qing Zhang; De-an Guo (Food Research International, 2025)

One-step open-ring strategy for constructing sandwich-like metal–organic framework with highly selective removal of thorium - Meng-Jie Yang; An-Min Song; Qing Yang; Zhi Wu; Bin Lin; Ru-Ping Liang; Jian-Ding Qiu (Chemical Engineering Journal, 2025)

Sesquiterpenoids from the whole plants of Elephantopus mollis with cytotoxicity activities - Qiang Lin; Jing-Yi Du; Si-Yu Yang; Zhao-Chun Zhan; Qing Tang; Hui Sun; Jin-Lin Tan; Hai-Yue Zhao; Yao-Lan Li; Yu-Bo Zhang; Guo-Cai Wang (Natural Product Research, 2025)

Enhanced biodegradation of glyphosate by Chlorella sorokiniana engineered with exogenous purple acid phosphatase - Si-Fen Liu; Zhong-Chen Yi; Zi-Qiong Huang; Zhen-Dong Yuan; Yu-Cheng Yang; Yongteng Zhao; Qing-Yu He; Wei-Dong Yang; Hong-Ye Li; Carol Sze Ki Lin; Xiang Wang (Water Research, 2025)

Biofilm formation dynamics in long-distance water conveyance pipelines: Impacts of nutrient levels and metal stress - Yifan Hu; Ruiting Li; Kaiqin Bian; Qing Zhou; Yang Pan; Lin Ye; Aimin Li; Peng Shi (Water Research, 2025)

Chlorinated paraffins in particulate matter associated with asthma and its relative symptoms in school-aged children and adolescents: A cross-sectional survey in South China - Jing-Wen Huang; Wan-Ting He; Yun-Ting Zhang; Mo Yang; Nan-Xiang Jin; Ari Leskinen; Mika Komppula; Marjut Roponen; Li-Zi Lin; Zhao-Huan Gui; Ru-Qing Liu; Guang-Hui Dong; et al. (Science of The Total Environment, 2025)

Isomerization of glucose to fructose catalyzed by MgCl2 in water - Fengli Yang; Qing Xia; Guangpin Lin; Yi Su; Wei Lin; Huabing Zhang; Guobin Liang (Fuel, 2025)

Effects of rosmarinic acid covalent conjugation on the allergenicity and functional properties of egg white protein - Xuanpei Wang; Hao-Long Zeng; Jieli Shang; Yijie Chen; Lin Xu; Jine Wu; Zhiyong Gong; Xin Liu; Qing Yang (Food Hydrocolloids, 2025)

Leifsonia stereocauli sp. nov., Isolated from Stereocaulon tomentosum Fr. Lichen - Shu-Ya Zuo; Lian-Shuang Xiong; Qing Yuan; Guo-Hua Chen; Rui Yang; Li-Song Wang; Cheng-Lin Jiang; Xin-Yu Wang; Yi Jiang (Current Microbiology, 2025)

Understanding the Past to Preserve the Future: Genomic Insights Into the Conservation Management of a Critically Endangered Waterbird - Qing Chen; Hongzhou Lin; Chenqing Zheng; Elena A. Mudrik; Tatiana A. Kashentseva; Yalin Cheng; Zhiru Wang; Haiyan Zhou; Haixiang Zhou; Wenjuan Wang; Yang Liu (Molecular Ecology, 2025)
To ensure the success of genetic rescue, we must minimise the potential negative effects of outbreeding depression that may arise from selecting source populations. The difficulty in assessing the likelihood of outbreeding depression has hindered its consideration in endangered species conservation. However, genomic research offers feasible indications. Here, we conduct conservation genomic analyses on the East Asian (EA) population and the relict Western/Central Asian (WCA) population of the critically endangered Siberian crane ( Leucogeranus leucogeranus ). We aim to assess genetic rescue's potential advantages and disadvantages between the two populations. Our analysis shows genomic evidence of limited genetic differentiation between them. The persistent decline in population size due to historical climatic oscillations leads to a decrease in genetic diversity and an increase in inbreeding. The WCA population has excessive deleterious homozygous mutations than the EA population, suggesting suffering from inbreeding depression resulting from less effective purifying selection. Forward simulations support the increase in genetic load due to elevated levels of inbreeding compromises fitness during population collapse. We strongly recommend an urgent genetic rescue for the WCA population through population supplementation from the EA population. However, the continuous monitoring of fitness outcomes is required through captive breeding. This work provides useful insights into the genetic management of a critically endangered species and emphasises the importance of evaluating the likelihood of outbreeding depression through genomic approaches.

Carbon chain elongation characterizations of electrode-biofilm microbes in electro-fermentation - Wei-Tong Ren; Zi-Lin He; Yang Lv; Hua-Zhe Wang; Lin Deng; Shan-Shan Ye; Juan-Shan Du; Qing-Lian Wu; Wan-Qian Guo (Water Research, 2024)

ROS responsive nanozyme loaded with STING silencing for the treatment of sepsis-induced acute lung injury - Yin-jin Zhang; Ling-yang Chen; Feng Lin; Xia Zhang; Hai-fei Xiang; Qing Rao (Toxicology and Applied Pharmacology, 2024)

Association of anthropogenic heat with asthma and related symptoms among children in China: A novel index reflecting climate change - Feng-Wen Shan; Xuan Liu; Ming-Kun Sun; Zhengmin Qian; Michael G. Vaughn; Niraj R. Chavan; Shu-Li Xu; He-Hai Huang; Zhao-Huan Gui; Ru-Qing Liu; Li-Wen Hu; Li-Zi Lin; et al. (Sustainable Cities and Society, 2024)

Outdoor light at night is a modifiable environmental factor for metabolic syndrome: The 33 Communities Chinese Health Study (33CCHS) - Li-Wen Hu; Yan-Chen Gong; Hong-Xing Zou; Le-Bing Wang; Yanan Sun; Alejandro Godinez; Han-Yu Yang; Si-Han Wu; Shuo Zhang; Wen-Zhong Huang; Zhao-Huan Gui; Li-Zi Lin; et al. (Science of The Total Environment, 2024)

Corrigendum to “Revisiting the formation of lunar anorthosites via the Rb-Sr isotope systematics” [Lithos, volume 486–487, (2024) 107780] - Qing Zhou; Heng-Ci Tian; Liyu Shan; Sen Hu; Wei Yang; Maoyong He; Lei Zhang; Yangting Lin; Xianhua Li (Lithos, 2024)

Ultrasonic technology for predicting beef thawing degree and endpoint - Hongzhou Chen; Qing Sun; Lilei Xuan; Zitao Lin; Zeyu Yang; Xiaowei Huang; Zhihua Li; Wenjian Gao; Jun Ren; Jiyong Shi; Xiaobo Zou (Journal of Food Engineering, 2024)

Untargeted metabolomics and PacBio analysis on bioactive components and microbial community in co-fermentation of black soldier fly larva - He Liu; Xia Yang; Xiaolan Yu; Jiacong Lin; Shiliang Peng; Qing Li; Qingzhu Yang; Dingmei Wang; Qinfen Li (Food Research International, 2024)

An improved vector method for simultaneous analysis of removability and kinematics in block theory - Qin Chen; Qing-yang Zhu; Jun-lin Chen; Hai-bo Li; Xing-guo Yang; Jia-wen Zhou (Engineering Geology, 2024)

Inhibitory effect of rosmarinic acid on IgE-trigged mast cell degranulation in vitro and in vivo - Binmei Jia; Hao-Long Zeng; Jieli Shang; Xuanpei Wang; Lin Xu; Min Fang; Fengbo Zeng; Qing Yang (Molecular Biology Reports, 2024)

Retraction Note to: LPS Pretreatment Provides Neuroprotective Roles in Rats with Subarachnoid Hemorrhage by Downregulating MMP9 and Caspase3 Associated with TLR4 Signaling Activation - Ting-Hua Wang; Liu-Lin Xiong; Shuai-Fen Yang; Chao You; Qing-Jie Xia; Yang Xu; Piao Zhang; Shu-Fen Wang; Jia Liu (Molecular Neurobiology, 2024)

Efficacy and safety of 4-hydroxy-2-methyl-N-(5-methyl-2-thiazolyl)-2H-1, 2-benzothiazin-3-carboxamide 1,1-dioxide, a rapid-acting meloxicam formulation, for analgesia after orthopaedic surgery under general anaesthesia: a randomized controlled trial - Yingyong Zhou; Yan Jiang; Kaiming Duan; Qiongcan Li; Mengchang Yang; Qing Lei; Mingsheng Bao; Guijie Xie; Jie Sun; Liang Chen; Hongmei Zhou; Yanzhuo Zhang; et al. (Inflammopharmacology, 2024)

Molecular epidemiology of herpangina in the subcenter of Beijing, China: a surveillance study during 2021-2022 - Wan-Xue Zhang; Lin Zou; Yan Cui; Yiguo Zhou; Shan-Shan Zhang; Han Yang; Susu Ding; Qin-Yi Ma; Lu Xi; Ran-Ran Zheng; Juan Du; Jianming Zhang; et al. (Archives of Virology, 2024)

Devosia lacusdianchii sp. nov., an attached bacterium inhibited by metabolites from its symbiotic Microcystis - Qing-Lin Deng; Yao Xiao; Ru Jia; Xin Xie; Le Wang; Xin Wang; Jian-Yuan Yang; Qi-Gen Guo; Bing-Huo Zhang (Antonie van Leeuwenhoek, 2024)

The role of Nocardia seriolae-induced autophagy in the development of chronic inflammation in the liver and the formation of granulomas in largemouth bass (Micropterus salmoides) - Shang-Jie Bai; Zheng-Ran Jian; Sheng-Yu He; Lin-Feng Kuang; Zheng-Yang Zhou; Chen-Wang Lu; Zhen-Dong Zhong; Jie He; Quan-Xin Xiong; Shuang-Yan Xiao; Peng-Fei Li; Ming-Zhu Liu; et al. (Aquaculture, 2024)

Revisiting the formation of lunar anorthosites via the Rb Sr isotope systematics - Qing Zhou; Heng-Ci Tian; Liyu Shan; Sen Hu; Wei Yang; Maoyong He; Lei Zhang; Yangting Lin; Xianhua Li (Lithos, 2024)

Biochar modification accelerates soil atrazine biodegradation by altering bacterial communities, degradation-related genes and metabolic pathways - Yijie Chen; Zhen Zhen; Weilong Wu; Changhong Yang; Guiqiong Yang; Xiaofeng Li; Qing Li; Xiaolan Zhong; Junyong Yin; Zhong Lin; Dayi Zhang (Journal of Hazardous Materials, 2024)

Nickel sulfide nanorods encapsulated in Nitrogen-Doped carbon on nickel foam in situ derived from Saccharomycetes cerevisiae for the selective oxidation of biomass - Hao Chen; Si-Ru Chen; Qing Yang; Le-Xing You; Qun-Feng Ye; Ai-Jun Wang; Dong-Hai Lin; Yan-Xia Jiang; Shi-Gang Sun (Chemical Engineering Journal, 2024)

Neurotoxicity of fine and ultrafine particulate matter: A comprehensive review using a toxicity pathway-oriented adverse outcome pathway framework - Shuang-Jian Qin; Qing-Guo Zeng; Hui-Xian Zeng; Shen-Pan Li; John Andersson; Bin Zhao; Anna Oudin; Katja M. Kanninen; Pasi Jalava; Nan-Xiang Jin; Mo Yang; Li-Zi Lin; et al. (Science of The Total Environment, 2024)

First insight of the intergenerational effects of tri-n-butyl phosphate and polystyrene microplastics to Daphnia magna - Xiaoli Chen; Yijing Gan; Xinlu Yang; Lixiang Zhong; Menghuan Zhang; Mingfu Lin; Xian Qing; Jun Wang; Yumei Huang (Science of The Total Environment, 2024)

Female urinary incontinence in China after 15 years’ efforts: Results from large-scale nationwide surveys - Jiming Zhu; Haiyu Pang; Peicheng Wang; Yanhua Chen; Huihui Li; Qing Liu; Luwen Wang; Hangmei Jin; Liyan Gong; Jingyan Xie; Ting Lai; Aiyang Li; et al. (Science Bulletin, 2024)

Long-term ambient ozone exposure and childhood asthma, rhinitis, eczema, and conjunctivitis: A multi-city study in China - Zhao-Huan Gui; Zhan-Yu Guo; Yang Zhou; Shyamali Dharmage; Lidia Morawska; Joachim Heinrich; Zhang-Kai Cheng; Hui Gan; Zhi-Wei Lin; Dong-Ying Zhang; Jing-Wen Huang; Li-Zi Lin; et al. (Journal of Hazardous Materials, 2024)

Nonlinear impact of automobile industry agglomeration on CO2 emission: Incorporating urban characteristics in China - Keke Ji; Qing Yang; Hailong Zhao; Mingnan Zhao; Lei Wang; Kaili Ji; Xingxing Liu; Zipeng Lin; Yandi Zheng (Journal of Cleaner Production, 2024)

Novel method for reducing NDMA formation from daminozide during ozonation: Performances and mechanisms - Linfang Li; Qing Lin; Xiaobin Liao; Tianze Liu; Huan Qi; Qingsong Li; Menglan Gao; Jing Zou; Zhenming Zhou; Mingzhi Huang; Zhimin Yang (Journal of Cleaner Production, 2024)

Distribution of soil tardigrades as revealed by molecular identification across a large-scale area of Australia - Zi-Yang He; Hang-Wei Hu; Bao-Anh Thi Nguyen; Qing-Lin Chen; Anthony Weatherley; Michael Nash; Li Bi; Keren Wu; Ji-Zheng He (Soil Biology and Biochemistry, 2024)

Investigating the impact of ultrasound on the structural, physicochemical, and emulsifying characteristics of Dioscorin: Insights from experimental data and molecular dynamics simulation - Qi Gao; Yu-qi Yang; Hao-nan Nie; Bing-qing Wang; Xue Peng; Ning Wang; Jiang-kuo Li; Jia-jia Rao; You-lin Xue (Food Chemistry, 2024)

Identification and health risk assessment of volatile and semi-volatile migrants along with chemical elements in food contact water-borne coating paper - Qing-Hua Yang; Qin-Bao Lin; Xin-Yu Hua; Jia Liao; Shi-Qiang Lu; Ling-Yan Yan; Hong-Sheng Ma (Food Packaging and Shelf Life, 2024)

Association between outdoor light at night exposure and executive function in Chinese children - Han-Yu Yang; Si-Han Wu; Shuo Zhang; Hong-Xing Zou; Le-Bing Wang; Li-Zi Lin; Zhao-Huan Gui; Xiao-Wen Zeng; Bo-Yi Yang; Ru-Qing Liu; Guang-Hui Dong; Li-Wen Hu (Environmental Research, 2024)

Insight into response mechanism of aerobic granular sludge to combined nanoparticle stress: Nitrogen removal, microbial community and heavy metal resistance genes - Yu-Qi Li; Bai-Hang Zhao; Yu-Qing Zhang; Hai-Shan Yang; Bing-Lin Zhang (Chemical Engineering Journal, 2024)

In-situ modification of nickel electrode by coupling the microbial corrosion and microbial reduction using Shewanella oneidensis for enhanced electrocatalysis - Jun-Lin Li; Jian-Li Mi; Zhuo-Lin Qing; Hao Hu; Si-Yuan Jia; Jun-Ying Liu; Yang-Chun Yong (Chemical Engineering Journal, 2024)

Pichia pastoris composition expressed aerolysin mutant of Aeromonas veronii as an oral vaccine evaluated in zebrafish (Danio rerio) - Yuan-Yuan Yao; Qing-Shuang Zhang; Shu-Bin Liu; Hong-Wei Yang; Xing-Yu Chen; Ya-Lin Yang; Chen-Chen Gao; Chao Ran; Tsegay Teame; Zhen Zhang; Zhi-Gang Zhou (Marine Life Science & Technology, 2024)
Vaccines are one of the most practical means to stop the spreading of Aeromonas veronii in aquaculture. In this study, virulence factor aerolysin mutant NTaer which has lost its hemolytic activity was used as a target antigen. Pichia pastoris constitutive secretory expression NTaer (GS115-NTaer) was used as a potential safe oral vaccine to evaluate its effectiveness on zebrafish immunity. The result shows that vaccination of GS115- NTaer for four weeks did not affect the growth performance of the host, while eliciting an effective immune protective response. Compared with the control group, the GS115-NTaer could significantly up-regulate the relative expression level of the intestinal tight junction protein 1α ( TJP1α ) gene, and significantly increased the contents of lysozyme (LYZ), complement C3 and C4 in the gut, indicating that the innate immune response of the fish was activated. The relative gene expression levels of macrophage-expressed gene 1 ( MPEG1 ) and T cell receptor ( TCR-α ) in the gut, and MPEG1 , CD4 , CD8 , TCR-α , GATA3, and T-bet in the spleen were all increased significantly, indicating that the cellular immune response of the fish was activated. Furthermore, the contents of serum IgM and intestinal mucosa IgZ antibodies were significantly increased, which showed that humoral immunity was also activated. Moreover, inoculation with GS115-NTaer significantly changed the structure of gut microbiota. In particular, the relative ratio of (Firmicutes + Fusobacteriota + Bacteroidota)/Proteobacteria was significantly higher than that of the control and GS115 groups. Lastly, the vaccinated fish were challenged with A. veronii, and the relative percent survival of GS115 and the GS115-NTear groups was 14.28% and 33.43%. This improvement of immunity was not only due to the specific immune response but also attributed to the improvement of innate immunity and the gut microbiota which was demonstrated by the germ-free zebrafish model. Collectively, this study provides information on the effectiveness of GS115-NTear as an oral vaccine for the green prevention and control of A. veronii infection in fish aquaculture.

Advanced strategies for conversing and fixing sulfur during waste resins oxidation through Ca/Zn oxides enhanced Na2CO3-K2CO3 system - Xin Liu; Yong-De Yan; Yun Xue; Yang-Hai Zheng; Jing-Ping Wang; Qing-Guo Zhang; Yue-Lin Wang; Fu-Qiu Ma (Process Safety and Environmental Protection, 2024)

Genomic analysis of Alteromonas sp. M12 isolated from the Mariana Trench reveals its role in dimethylsulfoniopropionate cycling - Yue Lin; Min Zhang; Yu-Xiang Lai; Teng Liu; Meng Meng; Yan Sun; Yu Wang; Qing-Yu Dong; Chen-Xi Li; Meng-Xue Yu; Jin Cheng; Shu-Jun Liu; et al. (Marine Genomics, 2024)

Visible light-driven characterisation of AgI/CeO2/rGO nanocomposites and their application in levofloxacin degradation - Zhixin Ren; Lin Yang; Xiaoxue Tang; Qing Xu; Yanan Niu; Yuguang Lv; Mingyuan Liu (Journal of Environmental Chemical Engineering, 2024)

Three species of rape responded to cadmium and melatonin alleviating Cd-toxicity in species-specific strategy - Xiao-long Qin; Yu-qing Zhao; De-jun Zhang; Ke-yu Wang; Wen-hui Chen; Zi-Zhong Tang; Yang-er Chen; Shu Yuan; Lin Ye; Ming Yuan (Environmental Pollution, 2024)

Active prelithiation strategies for advanced lithium storage systems: A perspective from electrochemical mechanism to structural design and application - Bo Jin; Keyu Zhang; Geng Gao; Qing Zhao; Xinyu Jiang; Dingfang Cui; Keqi Chen; Xiang Lin; Liuliu Liu; Rui Yan; Bin Yang; Yaochun Yao (Chemical Engineering Journal, 2024)

Two-photon polymerization-based 3D micro-scaffolds toward biomedical devices - Wei Wang; Zi-Qing Chen; Bin Lin; Mei-Chen Liu; Yang Zhang; Shu-Juan Liu; Yang Li; Qiang Zhao (Chemical Engineering Journal, 2024)

Feedback of chain elongation microorganisms on iron-based conductive materials: Enhanced microbial functions and biotoxicity adaptation mechanisms - Wei-Tong Ren; Yang Lv; Zi-Lin He; Hua-Zhe Wang; Lin Deng; Shan-Shan Ye; Qing-Lian Wu; Wan-Qian Guo (Bioresource Technology, 2024)

Fungal metabolite altersolanol a exhibits potent cytotoxicity against human placental trophoblasts in vitro via mitochondria-mediated apoptosis - Ting Gu; Yuting Wen; Qian Zhou; Wei Yuan; Haichun Guo; Wen-Lin Chang; Qing Yang (Mycotoxin Research, 2024)

The sensing of circRNA with tetrahedral DNA nanostructure modified microfluidic chip - Shiliang He; Lei Chen; Zhuolang Chen; Guihao Zhang; Yongjin Huang; Huaxiao Zheng; Qing Yang; Zhuoxi Mo; Xinyi Lin; Jiancheng Wen (Analytica Chimica Acta, 2024)

Relay intercropping boosts soybean recovery growth and delays nodule senescence to achieve yield advantages - Ping Chen; Benchuan Zheng; Huan Yang; Qing Du; Zhidan Fu; Kai Luo; Yilin Li; Ping Lin; Xihong Peng; Tian Pu; Yushan Wu; Xiaochun Wang; et al. (Agriculture, Ecosystems & Environment, 2024)

Application of C30 tetracyclic polyprenoids as effective biomarker in oil-to source rock correlation in the Zhu III depression, Zhujiangkou Basin, northern South China - Lei Lan; Youchuan Li; Shuchun Yang; Yang Ouyang; Wenjing Ding; Qing Lin; Shanshan Zhou (Acta Oceanologica Sinica, 2024)

Fertilization regulates global thresholds in soil bacteria - Cai Chen; Shu‐Le Li; Qing‐Lin Chen; Manuel Delgado‐Baquerizo; Zhao‐Feng Guo; Fenghua Wang; Yao‐Yang Xu; Yong‐Guan Zhu (Global Change Biology, 2024)
Global patterns in soil microbiomes are driven by non‐linear environmental thresholds. Fertilization is known to shape the soil microbiome of terrestrial ecosystems worldwide. Yet, whether fertilization influences global thresholds in soil microbiomes remains virtually unknown. Here, utilizing optimized machine learning models with Shapley additive explanations on a dataset of 10,907 soil samples from 24 countries, we discovered that the microbial community response to fertilization is highly dependent on environmental contexts. Furthermore, the interactions among nitrogen (N) addition, pH, and mean annual temperature contribute to non‐linear patterns in soil bacterial diversity. Specifically, we observed positive responses within a soil pH range of 5.2–6.6, with the influence of higher temperature (>15°C) on bacterial diversity being positive within this pH range but reversed in more acidic or alkaline soils. Additionally, we revealed the threshold effect of soil organic carbon and total nitrogen, demonstrating how temperature and N addition amount interacted with microbial communities within specific edaphic concentration ranges. Our findings underscore how complex environmental interactions control soil bacterial diversity under fertilization.

Mitochondrial damage and activation of NLRP3 induced by Yersinia ruckeri infection play an important role in the occurrence of diffuse acute inflammation of channel catfish (Ictalurus punctatus) - Chen-Wang Lu; Jie He; Quan-Xin Xiong; Zhen-Dong Zhong; Bin Yang; Sheng Lian; Meng-Meng Wang; Shang-Jie Bai; Lin-Feng Kuang; Zheng-Yang Zhou; Zheng-Ran Jian; Yuan-Chang Gao; et al. (Aquaculture, 2024)

Experimental investigation on the flow boiling of R134a in a plate heat exchanger with mini-wavy corrugations - Wei-chao Lao; Yi-dong Fang; Qing-hu Chen; Lin-jie Xu; Hui-nan Yang; Yu-qi Huang (International Journal of Refrigeration, 2024)

Ultrasound-responsive metal–organic framework-based nanosystem for sonodynamic therapy/amplified ferroptosis/IDO-blockade osteosarcoma immunotherapy - Qingjian Lei; Wei Zhou; Shijie Gao; Ningxiang Sun; Bo Wang; Haixia Yang; Jie Wang; Yu Zhao; Qing Chen; Jian Tian; Lin Cai; Feifei Yan (Chemical Engineering Journal, 2024)

Insect cuticle-inspired design of sustainably sourced composite bioplastics with enhanced strength, toughness and stretch-strengthening behavior - Nan Wu; Qiaoxia Lin; Fei Shao; Lei Chen; Haoyue Zhang; Kaiwen Chen; Jinrong Wu; Guirong Wang; Huanan Wang; Qing Yang (Carbohydrate Polymers, 2024)

Regulatory effect of Yinchenhao decoction on bile acid metabolism to improve the inflammatory microenvironment of hepatocellular carcinoma in mice - Jian Shi; Lin Zhu; Bang-Yi Tang; Wan-Qing Yang; Sheng-Yan Xi; Chen-Long Zhang; Peng-Fei Li; Yu-Jie Wang; Kai-Hang Guo; Jing-Ru Huang; Chen-Rui Huang; Zhou-Xin Yu; et al. (Journal of Natural Medicines, 2024)

Therapeutic effects and mechanisms of isoxanthohumol on DSS-induced colitis: regulating T cell development, restoring gut microbiota, and improving metabolic disorders - Ya-Na Yang; Bing Han; Mao-Qing Zhang; Na-Nan Chai; Feng-Lin Yu; Wen-Hui Qi; Meng-Yuan Tian; Dong-Zhi Sun; Ying Huang; Qing-Xin Song; Yan Li; Mao-Cui Zhu; et al. (Inflammopharmacology, 2024)

Correction to: Near‑global summer circulation response to the spring surface temperature anomaly in Tibetan Plateau –– the GEWEX/LS4P first phase experiment - Yang Zhang; Yan Pan; Yongkang Xue; Ismaila Diallo; Xubin Zeng; Shuting Li; J. David Neelin; William K. M. Lau; Aaron A. Boone; Frederic Vitart; Tandong Yao; Qi Tang; et al. (Climate Dynamics, 2024)

Root rot induces a core assemblage of bacterial microbiome to prevent disease infection in Sanqi ginseng - Baoying Wang; Qing Xia; Yulan Lin; Fugang Wei; Shaozhou Yang; Chuanchao Dai; Xinqi Huang; Jinbo Zhang; Zucong Cai; Jun Zhao (Applied Soil Ecology, 2024)

Carboxymethyl chitosan different durations induces disease resistance of grapefruit by modulating ascorbate-glutathione cycle and cell wall metabolism - Huayu Wu; Fang Wang; Qing Yang; Junrong Tang; Lin Chen; Zhengjun Shi; Xiahong He; Jia Deng (Postharvest Biology and Technology, 2024)

Positive association between chlorinated paraffins and the risk of allergic diseases in children and adolescents - Jing-Wen Huang; Ya-Ying Bai; Dao-Sen Wang; Wan-Ting He; Jing-Lin Zhang; Hai-Xin Tu; Jing-Yao Wang; Yun-Ting Zhang; Qi-Zhen Wu; Shu-Li Xu; He-Hai Huang; Mo Yang; et al. (Journal of Hazardous Materials, 2024)

Influence of desiccation during freeze-thaw cycles on volumetric shrinkage and tensile strength of compacted clayey soils - Yao Wei; Chao-Sheng Tang; Cheng Zhu; Qing Cheng; Yang Lu; Lin Li; Ben-Gang Tian; Bin Shi (Engineering Geology, 2024)

Toxicological evaluation and concentration of airborne PM0.1 in high air pollution period in Guangzhou, China - Mo Yang; Qi-Zhen Wu; Yun-Ting Zhang; Ari Leskinen; Xin-Feng Wang; Mika Komppula; Henri Hakkarainen; Marjut Roponen; Nan-Xiang Jin; Wei-Hong Tan; Shu-Li Xu; Li-Zi Lin; et al. (Science of The Total Environment, 2024)

Slc43a2+ T cell metastasis from spleen to brain in RGNNV infected teleost - Qing Wang; Yali Liu; Minlin Zhang; Min Yang; Jiantao Liang; Xiaoling Zuo; Shaowen Wang; Xianze Jia; Huihong Zhao; Han Jiang; Qiang Lin; Qiwei Qin (Science China Life Sciences, 2024)

Near-global summer circulation response to the spring surface temperature anomaly in Tibetan Plateau –– the GEWEX/LS4P first phase experiment - Yang Zhang; Yan Pan; Yongkang Xue; Ismaila Diallo; Xubin Zeng; Shuting Li; J. David Neelin; William K. M. Lau; Aaron A. Boone; Frederic Vitart; Tandong Yao; Qi Tang; et al. (Climate Dynamics, 2024)
Subseasonal to seasonal (S2S) prediction of droughts and floods is one of the major challenges of weather and climate prediction. Recent studies suggest that the springtime land surface temperature/subsurface temperature (LST/SUBT) over the Tibetan Plateau (TP) can be a new source of S2S predictability. The project “Impact of Initialized Land Surface Temperature and Snowpack on Subseasonal to Seasonal Prediction (LS4P)” was initiated to study the impact of springtime LST/SUBT anomalies over high mountain areas on summertime precipitation predictions. The present work explores the simulated global scale response of the atmospheric circulation to the springtime TP land surface cooling by 16 current state-of-the-art Earth System Models (ESMs) participating in the LS4P Phase I (LS4P-I) experiment. The LS4P-I results show, for the first time, that springtime TP surface anomalies can modulate a persistent quasi-barotropic Tibetan Plateau-Rocky Mountain Circumglobal (TRC) wave train from the TP via the northeast Asia and Bering Strait to the western part of the North America, along with the springtime westerly jet from TP across the whole North Pacific basin. The TRC wave train modulated by the TP thermal anomaly play a critical role on the early summer surface air temperature and precipitation anomalies in the regions along the wave train, especially over the northwest North America and the southern Great Plains. The participant models that fail in capturing the TRC wave train greatly under-predict climate anomalies in reference to observations and the successful models. These results suggest that the TP LST/SUBT anomaly via the TRC wave train is the first order source of the S2S variability in the regions mentioned. Furthermore, the TP surface temperature anomaly can influence the Southern Hemispheric circulation by generating cross-equator wave trains. However, the simulated propagation pathways from the TP into the Southern Hemisphere show large inter-model differences. More dynamical understanding of the TRC wave train as well as its cross-equator propagation into the Southern Hemisphere will be explored in the newly launched LS4P phase II experiment.

Remote effects of Tibetan Plateau spring land temperature on global subseasonal to seasonal precipitation prediction and comparison with effects of sea surface temperature: the GEWEX/LS4P Phase I experiment - Yongkang Xue; Ismaila Diallo; Aaron A. Boone; Yang Zhang; Xubin Zeng; William K. M. Lau; J. David Neelin; Tandong Yao; Qi Tang; Tomonori Sato; Myung-Seo Koo; Frederic Vitart; et al. (Climate Dynamics, 2024)
The prediction skill for precipitation anomalies in late spring and summer months—a significant component of extreme climate events—has remained stubbornly low for years. This paper presents a new idea that utilizes information on boreal spring land surface temperature/subsurface temperature (LST/SUBT) anomalies over the Tibetan Plateau (TP) to improve prediction of subsequent summer droughts/floods over several regions over the world, East Asia and North America in particular. The work was performed in the framework of the GEWEX/LS4P Phase I (LS4P-I) experiment, which focused on whether the TP LST/SUBT provides an additional source for subseasonal-to-seasonal (S2S) predictability. The summer 2003, when there were severe drought/flood over the southern/northern part of the Yangtze River basin, respectively, has been selected as the focus case. With the newly developed LST/SUBT initialization method, the observed surface temperature anomaly over the TP has been partially produced by the LS4P-I model ensemble mean, and 8 hotspot regions in the world were identified where June precipitation is significantly associated with anomalies of May TP land temperature. Consideration of the TP LST/SUBT effect has produced about 25–50% of observed precipitation anomalies in most hotspot regions. The multiple models have shown more consistency in the hotspot regions along the Tibetan Plateau-Rocky Mountain Circumglobal (TRC) wave train. The mechanisms for the LST/SUBT effect on the 2003 drought over the southern part of the Yangtze River Basin are discussed. For comparison, the global SST effect has also been tested and 6 regions with significant SST effects were identified in the 2003 case, explaining about 25–50% of precipitation anomalies over most of these regions. This study suggests that the TP LST/SUBT effect is a first-order source of S2S precipitation predictability, and hence it is comparable to that of the SST effect. With the completion of the LS4P-I, the LS4P-II has been launched and the LS4P-II protocol is briefly presented.

Relationship of single and co-exposure of per-and polyfluoroalkyl substances and their alternatives with uric acid: A community-based study in China - Li-Xia Liang; Li-Zi Lin; Mohammed Zeeshan; Yang Zhou; Yong-Xiang Tang; Chu Chu; Yun-Ting Zhang; Ru-Qing Liu; Wenru Feng; Guang-Hui Dong (Journal of Hazardous Materials, 2024)

Aboveground plants determine the exchange of pathogens within air-phyllosphere-soil continuum in urban greenspaces - Changyi Lu; Zufei Xiao; Hu Li; Ruixia Han; Anqi Sun; Qian Xiang; Zhe Zhu; Gang Li; Xiaoru Yang; Yong-Guan Zhu; Qing-Lin Chen (Journal of Hazardous Materials, 2024)

Leaching and evolution of anthocyanins and aroma compounds during Cabernet Sauvignon wine fermentation with whole-process skin-seed contact - Xue-Chen Yao; Hua-Lin Zhang; Xin-Rui Ma; Nong-Yu Xia; Chang-Qing Duan; Wei-Ming Yang; Qiu-Hong Pan (Food Chemistry, 2024)

Contrasting range changes of Bergenia (Saxifragaceae) species under future climate change in the Himalaya and Hengduan Mountains Region - Li Qiu; Qing-Li Fu; Hans Jacquemyn; Kevin S. Burgess; Jia-Jing Cheng; Zhi-Qiong Mo; Xiao-Dong Tang; Bo-Yun Yang; Shao-Lin Tan (Theoretical and Applied Climatology, 2024)

Anemoside B4, a new pyruvate carboxylase inhibitor, alleviates colitis by reprogramming macrophage function - Qing-hua Liang; Qiu-rong Li; Zhong Chen; Li-juan Lv; Yu Lin; Hong-lv Jiang; Ke-xin Wang; Ming-yue Xiao; Nai-xin Kang; Peng-fei Tu; Shi-liang Ji; Ke-jun Deng; et al. (Inflammation Research, 2024)

Pelagibacterium flavum sp. nov., Isolated from Soil Sample - Xue-Mei Chen; Zu-Zhen Yang; Si-Rong He; Lian-Shuang Xiong; Qing Yuan; Shu-Ya Zuo; Cheng-Lin Jiang; Yi Jiang (Current Microbiology, 2024)

Establishment of a TaqMan probe‐based qPCR assay for detecting microsporidia Enterospora epinepheli in grouper - Quan‐lin Liu; Yuan Wang; Jie Chen; Guo‐qing Pan; Yan‐Feng Yue; Ze‐Yang Zhou; Wen‐hong Fang (Journal of Fish Diseases, 2024)
Enterospora epinepheli is an intranuclear microsporidian parasite causing serious emaciative disease in hatchery‐bred juvenile groupers ( Epinephelus spp.). Rapid and sensitive detection is urgently needed as its chronic infection tends to cause emaciation as well as white faeces syndrome and results in fry mortality. This study established a TaqMan probe‐based real‐time quantitative PCR assays targeting the small subunit rRNA (SSU) gene of E. epinepheli. The relationship between the standard curve of cycle threshold (Ct) and the logarithmic starting quantity (SQ) was determined as Ct = −3.177 lg (SQ) + 38.397. The correlation coefficient ( R 2 ) was 0.999, and the amplification efficiency was 106.4%. The detection limit of the TaqMan probe‐based qPCR assay was 1.0 × 10 1 copies/μL and that is 100 times sensitive than the traditional PCR method. There is no cross‐reaction with other aquatic microsporidia such as Ecytonucleospora hepatopenaei , Nucleospora hippocampi , Potaspora sp., Ameson portunus. The intra‐assay and inter‐assay showed great repeatability and reproducibility. In addition, the test of clinical samples showed that this assay effectively detected E. epinepheli in the grouper's intestine tissue. The established TaqMan qPCR assays will be a valuable diagnostic tool for the epidemiological investigation as well as prevention and control of E. epinepheli .

Pivotal Role of GSTO2 in Ferroptotic Neuronal Injury After Intracerebral Hemorrhage - Li Lin; Xiao-Na Li; Zhen-Yan Xie; Yong-Zhen Hu; Qing-Shan Long; Yi-Qi Wen; Xiao-Bing Wei; Li-Yang Zhang; Xue-Song Li (Journal of Molecular Neuroscience, 2024)
Previous research has found that an adaptive response to ferroptosis involving glutathione peroxidase 4 (GPX4) is triggered after intracerebral hemorrhage. However, little is known about the mechanisms underlying adaptive responses to ferroptosis. To explore the mechanisms underlying adaptive responses to ferroptosis after intracerebral hemorrhage, we used hemin-treated HT22 cells to mimic brain injury after hemorrhagic stroke in vitro to evaluate the antioxidant enzymes and performed bioinformatics analysis based on the mRNA sequencing data. Further, we determined the expression of GSTO2 in hemin-treated hippocampal neurons and in a mouse model of hippocampus-intracerebral hemorrhage (h-ICH) by using Western blot. After hemin treatment, the antioxidant enzymes GPX4, Nrf2, and glutathione (GSH) were upregulated, suggesting that an adaptive response to ferroptosis was triggered. Furthermore, we performed mRNA sequencing to explore the underlying mechanism, and the results showed that 2234 genes were differentially expressed. Among these, ten genes related to ferroptosis (Acsl1, Ftl1, Gclc, Gclm, Hmox1, Map1lc3b, Slc7a11, Slc40a1, Tfrc, and Slc39a14) were altered after hemin treatment. In addition, analysis of the data retrieved from the GO database for the ten targeted genes showed that 20 items on biological processes, 17 items on cellular components, and 19 items on molecular functions were significantly enriched. Based on the GO data, we performed GSEA and found that the glutathione metabolic process was significantly enriched in the hemin phenotype. Notably, the expression of glutathione S-transferase omega (GSTO2), which is involved in glutathione metabolism, was decreased after hemin treatment, and overexpression of Gsto2 decreased lipid reactive oxygen species level in hemin-exposed HT22 cells. In addition, the expression of GSTO2 was also decreased in a mouse model of hippocampus-intracerebral hemorrhage (h-ICH). The decreased expression of GSTO2 in the glutathione metabolic process may be involved in ferroptotic neuronal injury following hemorrhagic stroke.

Nocardia seriolae mediates granulomatous chronic inflammation of spleen in Micropterus salmoides through necroptosis - Zheng-Yang Zhou; Sheng-Yu He; Chen-Wang Lu; Shang-Jie Bai; Lin-Feng Kuang; Bin Yang; Sheng Lian; Zheng-Ran Jian; Meng-Meng Wang; Shuang-Yan Xiao; Qing Yu; Ming-Zhu Liu; et al. (Aquaculture, 2024)

Screening of cadmium-chromium-tolerant strains and synergistic remediation of heavy metal-contaminated soil using king grass combined with highly efficient microbial strains - Fan Liu; Kailu Zhang; Yang Zhao; Dong Li; Xiaoyan Sun; Li Lin; Huiping Feng; Qing Huang; Zhiqiang Zhu (Science of The Total Environment, 2024)

PD-L1 expression guidance on sintilimab versus pembrolizumab with or without platinum-doublet chemotherapy in untreated patients with advanced non-small cell lung cancer (CTONG1901): A phase 2, randomized, controlled trial - Si-Yang Maggie Liu; Jie Huang; Jia-Yi Deng; Chong-Rui Xu; Hong-Hong Yan; Ming-Yi Yang; Yang-Si Li; E-E Ke; Ming-Ying Zheng; Zhen Wang; Jia-Xin Lin; Bin Gan; et al. (Science Bulletin, 2024)

Bimetallic ZIF-derived heteroatomic-doped bioanode catalysts for enhanced power production in microbial fuel cells - Liuqingying Yang; Ye Chen; Qing Wen; Cunguo Lin; Haiping Gao; Zhenghui Qi; Xu Pan (Fuel, 2024)

Effects of yeast screened from traditional fermented milk on commercial fermented milk as adjunct flavor culture - Hai-yan Kang; Xiao-lin Ao; Qing Tang; Hongli Li; Yang Fan; Ai-ping Liu; Li-kou Zou; Shu-liang Liu; Yong Yang; Ning Zhao; Jian-long Li (Food Bioscience, 2024)

Perturbation of IP3R-dependent endoplasmic reticulum calcium homeostasis by PPARδ-activated metabolic stress leads to mouse spermatocyte apoptosis: A direct mechanism for perfluorooctane sulfonic acid-induced spermatogenic disorders - Wang Yang; Xi Ling; Shijun He; Haonan Cui; Lihong Wang; Zeyu Yang; Huihui An; Peng Zou; Qing Chen; Lei Sun; Huan Yang; Jinyi Liu; et al. (Environmental Pollution, 2024)

Evaporation and desiccation cracking of soils: Experiment evidence and insight on the freeze-thaw cycle dependence - Yao Wei; Chao-Sheng Tang; Yang Lu; Mingli Zhang; Qing Cheng; Lin Li; Bin Shi (Engineering Geology, 2024)

The role of a small molecular dipole moment for efficient non-doped deep blue thermally activated delayed fluorescence emitters - Hong-Ji Tan; Jie-Rong Yu; Zhi-Zhong Lin; Guo-Xi Yang; Zhi-Qiang Long; Ying-Lan Deng; Ze-Lin Zhu; Xian-Kai Chen; Jing-Xin Jian; Qing-Xiao Tong; Chun-Sing Lee (Chemical Engineering Journal, 2024)

Peroxisome Proliferator-Activated Receptor-γ Coactivator-1α in the Spotlight with Multiple Sclerosis - Ya-Na Yang; Mao-Qing Zhang; Feng-Lin Yu; Bing Han; Ming-Yue Bao; Yan He; Xing Li; Yuan Zhang (Neuroscience Bulletin, 2024)

Effects of sub-chronic exposure to microcystin-LR on the endocrine system of male rats - Yu-Ting Wang; Qian-Hui Wu; Liang Chen; John P. Giesy; Lin-Lin Xu; Wen-Li Xu; Jun He; Ting Shi; Yi-Qing Liu; Shi-Man Xiao; Ye-Ke Wang; Feng Chen; et al. (Science of The Total Environment, 2024)

Otolith microchemistry reveals diverse habitat uses and migratory patterns of two Coilia species (Engraulidae) in the Min River Estuary, southern China - Qing Xu; Qing-qiang Ren; Tao Jiang; Bai-an Lin; Xiao-bin Jiang; Jian Yang; Min Liu (Marine Environmental Research, 2024)

Association of adverse fetal outcomes with placental inflammation after oral gestational exposure to hexafluoropropylene oxide dimer acid (GenX) in Sprague-Dawley rats - Di Lv; Hongyun Liu; Qi An; Chengwei Lei; Yanxuan Wang; Jin Sun; Chuanhai Li; Yongfeng Lin; Qing Dong; Zhugen Yang; Kui Che; Wendong Liu; et al. (Journal of Hazardous Materials, 2024)

Electrostatic self-assembled nickel cobalt sulfide/Ti3C2 Mxene as a bio-capacitive anode for specific attracting sulfur-cycling bacteria and regulating extracellular electron transfer efficiency - Haitao Xu; Ye Chen; Qing Wen; Cunguo Lin; Haiping Gao; Zhenghui Qiu; Liuqingying Yang; Xu Pan (Journal of Cleaner Production, 2024)

Pressure–temperature–time path of ultrahigh-pressure metamorphic terranes constrained by zircon petrochronology: A case study of orthogneisses from the northern Sulu belt, China - Peng Feng; Hao Deng; Yang Zhang; Qing-Lin Sui; Hai-Yang He; Yan-Shi Xie; Liang Chen; Xian-Zhe Duan; Wen-Zhou Xiao; Xia-Wen Li; Nan Li (Journal of Asian Earth Sciences, 2024)

Variations in the pore structure and fluid mobility under anionic surfactant assisted matrix acidification of coal based on nuclear magnetic resonance T1-T2 spectra - Jiawei He; He Li; Jiexin Lu; Wei Yang; Baiquan Lin; Meng Liu; Yi Lu; Shiliang Shi; Zheng Wang; Qing Ye (Fuel, 2024)

Expression of polyphenol oxidase of Litopenaeus vannamei and its characterization - Qian Hong; Yu-Lei Chen; Duanquan Lin; Ru-Qing Yang; Kai-Yuan Cao; Ling-Jing Zhang; Yi-Ming Liu; Le-Chang Sun; Min-Jie Cao (Food Chemistry, 2024)

Global, regional, and national burden of ischemic heart disease attributable to ambient PM2.5 from 1990 to 2019: An analysis for the global burden of disease study 2019 - Li-Hao Guo; Li-Zi Lin; Yang Zhou; Bin Jalaludin; Lidia Morawska; Shyamali C. Dharmage; Luke D. Knibbs; Guo-Feng Huang; Duo-Hong Chen; Huimin Ma; Meng Gao; Joachim Heinrich; et al. (Environmental Research, 2024)

Effects of low-concentration spinetoram wax-based bait stations on Bactrocera dorsalis (Diptera: Tephritidae) - Jia Lin; Guoqing Yue; Kang Xiao; Deqing Yang; Xuxing Hao; Minlin Zheng; Pumo Cai; Qing'e Ji (Pesticide Biochemistry and Physiology, 2023)

The first identification and functional analysis of two drosophila mothers against decapentaplegic protein genes (SpSmad1 and SpSmad2/3) and their involvement in the innate immune response in Scylla paramamosain - Bang-ze Li; Chen-yang Lin; Wen-bin Xu; Yan-mei Zhang; Qing-jun Shao; Wei-ren Dong; Miao-an Shu (Fish & Shellfish Immunology, 2023)

Point-to-face assembled carbon architecture targeting photothermal and electrothermal synergetic conversion and management for efficient cleanup of crude-oil spills - Lin Li; Jiarong Wang; Chaorui Xue; Qing Chang; Jinlong Yang; Shengliang Hu (Chemical Engineering Journal, 2023)

3D binder-free nanoarchitecture design of porous silicon/graphene fibers for ultrastable lithium storage - Yongbiao Mu; Ruijie Zhang; Bu-ke Wu; Ming Yang; Youqi Chu; Qing Zhang; Lingfeng Zou; Xianbin Wei; Zifan Liao; Haixiang Ren; Yiju Li; Lin Zeng (Chemical Engineering Journal, 2023)

A shared role of the myocardin-family transcriptional coactivators in cardiomyocyte maturation - Yuxuan Guo; Yangpo Cao; Blake D. Jardin; Neil Mazumdar; Congting Guo; Luzi Yang; Junsen Lin; Zhan Chen; Qing Ma; Mingming Zhao; Erdan Dong; William T. Pu (Science China Life Sciences, 2023)

Reexamining the Causes and Effects of Cholesterol Deposition in the Brains of Patients with Alzheimer’s Disease - Ze-Lin Hu; Yang-Qi Yuan; Zhen Tong; Mei-Qing Liao; Shun-Ling Yuan; Ye Jian; Jia-Lun Yang; Wen-Feng Liu (Molecular Neurobiology, 2023)

Ecosystem responses dominate the trends of annual gross primary productivity over terrestrial ecosystems of China during 2000–2020 - Xian-Jin Zhu; Gui-Rui Yu; Zhi Chen; Wei-Kang Zhang; Lang Han; Qiu-Feng Wang; Hua Qi; Meng Yang; Zhao-Gang Liu; Xiao-Jun Dou; Le-Xin Ma; Shi-Ping Chen; et al. (Agricultural and Forest Meteorology, 2023)

Reassessing the classification of Chang'e-5 basalts using pyroxene composition - Heng-Ci Tian; Wei Yang; Yubing Gao; Qing Zhou; Renhao Ruan; Yangting Lin; Xianhua Li; Fuyuan Wu (Lithos, 2023)

Development of a duplex PCR for the simultaneous detection of EHP and IHHNV and analysis of the correlation between these two pathogens - Yang Gao; Cai-Yi Chen; Zheng Cao; Ru-Qing Yuan; Lin-Rui Chang; Ting Li; Ling-Jun Si; Dong-Chun Yan; Fan Li (Journal of Invertebrate Pathology, 2023)

Headspace single drop microextraction based visual colorimetry for highly sensitive, selective and matrix interference-resistant determination of sulfur dioxide in food samples - Jie Zhou; Xiaojie Lin; Li Zhao; Ke Huang; Qing Yang; Huimin Yu; Xiaoli Xiong (Food Chemistry, 2023)

Developmental dynamics of the single nucleus regulatory landscape of pig hippocampus - Siyu Yang; Dong Chen; Lei Xie; Xiaoxiao Zou; Yanyuan Xiao; Lin Rao; Tianxiong Yao; Qing Zhang; Liping Cai; Fei Huang; Bin Yang; Lusheng Huang (Science China Life Sciences, 2023)

Homozygous variants in CDC23 cause female infertility characterized by oocyte maturation defects - Huizhen Fan; Zhou Zhou; Wei Zheng; Yichun Guan; Qingxia Meng; Wenjing Wang; Jie Dong; Liuxia Wan; Jiawei Zhu; Yang Zeng; Ruyi Liu; Hao Gu; et al. (Human Genetics, 2023)

The modification of meteorological factors on the relationship between air pollution and periodontal diseases: an exploration based on different interaction strategies - Kai Huang; Lin-Fei Feng; Zhe-Ye Liu; Zhen-Hua Li; Yi-Cheng Mao; Xin-Qiang Wang; Jia-Wen Zhao; Kang-Di Zhang; Ying-Qing Li; Jie Wang; Wen-Jie Yu; Xin Cheng; et al. (Environmental Geochemistry and Health, 2023)

Indicator of climate variability: low treeline displacement in arid valleys of mountain areas, China - Wei-po Yan; Qing Wang; Ya-lin Guo; Qi Hu; Min Yang; Yi-da An (Journal of Mountain Science, 2023)

Arbuscular mycorrhiza changes plant facilitation patterns and increases resource use efficiency in intercropped annual plants - Shuang-Guo Zhu; Hai-Xia Duan; Hong-Yan Tao; Li Zhu; Rui Zhou; Yu-Miao Yang; Xiao-Lin Zhang; Wen-Ying Wang; Hao Zhu; Wei Zhang; Ren-Qing Wang; Xiu-Ping Tao; et al. (Applied Soil Ecology, 2023)

The conversion of organic sulfur and strontium into inorganic compounds during the molten salt oxidation of mixed resin - Xin Liu; Yong-De Yan; Yang-Hai Zheng; Wen-Da Xu; Yun Xue; Jing-Ping Wang; Qing-Guo Zhang; Yue-Lin Wang; Fu-Qiu Ma (Journal of Environmental Chemical Engineering, 2023)

Combining HUMSC secretome and a conductive hydrogel enhances angiogenesis and electrical transmission at myocardial infarct sites to support cardiac repair - Shu-yi He; Lin-yu Long; Zhi-cun Wang; Wen-qi Liu; Wen Zhang; Cheng Hu; Xiao-feng Wu; Ruiqi Dong; Hong-song Fan; Qing-Jiang; Ying-ying Tong; Guang-hua Yang; et al. (Chemical Engineering Journal, 2023)

Heart valve-inspired self-lubricating anticoagulant surfaces - Yang Cheng; Zhiwei Yang; Xiaodan Gou; Qing Yang; Zichen Zhang; Shiyu Cui; Yuhua Ren; Lihong Fan; Haifeng Zhang; Zheng Fang; Yu Lu; Lin Kai; et al. (Chemical Engineering Journal, 2023)

TERT transcription and translocation into mitochondria regulate benzo[a]pyrene/BPDE-induced senescence and mitochondrial damage in mouse spermatocytes - Haonan Cui; Wang Yang; Shijun He; Zili Chai; Lihong Wang; Guowei Zhang; Peng Zou; Lei Sun; Huan Yang; Qing Chen; Jinyi Liu; Jia Cao; et al. (Toxicology and Applied Pharmacology, 2023)

Bioavailability of micro/nanoplastics and their associated polycyclic aromatic hydrocarbons to Daphnia Magna: Role of ingestion and egestion of plastics - Yao Li; Xinghui Xia; Jie Zhang; Xiaohan Lin; Yidi Zhang; Haotian Wang; Yang Li; Qing Zhang; Shangwei Zhang (Science of The Total Environment, 2023)

The association between childhood adiposity in northeast China and anthropogenic heat flux: A new insight into the comprehensive impact of human activities - Hong-Zhi Zhang; Dao-Sen Wang; Si-Han Wu; Guo-Feng Huang; Duo-Hong Chen; Hui-Min Ma; Yun-Ting Zhang; Li-Hao Guo; Li-Zi Lin; Zhao-Huan Gui; Ru-Qing Liu; Li-Wen Hu; et al. (International Journal of Hygiene and Environmental Health, 2023)

Monitoring regional soil organic matter content using a spatiotemporal model with time-series synthetic Landsat images - Mei-Wei Zhang; Xiao-Qing Wang; Xiao-Gang Ding; Hua-Lei Yang; Qian Guo; Ling-Tao Zeng; Yu-Pei Cui; Xiao-Lin Sun (Geoderma Regional, 2023)

Highly efficient catalytic CO oxidation by balancing the crystal and mesoporous structure of Ta2O5 carrier combined with cobalt - Haijian Qin; Zelong Yang; Qing Xia; PeifeiYao; Chunzhi Zheng; Guangpin Lin; Zhaolian Ye; Songjian Zhao; Fengli Yang (Fuel, 2023)

Performance and mechanism of calcium peroxide reducing H2S production from sludge anaerobic fermentation - Yunhao Xu; Qizi Fu; Wenming Wang; Fan Yang; Xuemei Li; Fengming Song; Yanguang Qing; Ziqi Lin; Weiqi Long; Dongbo Wang (Chemical Engineering Journal, 2023)

The associations of non-essential metal mixture with fasting plasma glucose among Chinese older adults without diabetes - Jing-Yuan Lei; Pan-Pan Wang; Hong-Li Wang; Yuan Wang; Liang Sun; Bing Hu; Su-Fang Wang; Dong-Mei Zhang; Gui-Mei Chen; Chun-Mei Liang; Fang-Biao Tao; Lin-Sheng Yang; et al. (Environmental Science and Pollution Research, 2023)

Antimony(III) removal by biogenic manganese oxides formed by Pseudomonas aeruginosa PA-1: kinetics and mechanisms - Qing Li; Yun He; Aijiang Yang; Xia Hu; Fang Liu; Jincheng Mu; Shixue Mei; Lin-Ping Yang (Environmental Science and Pollution Research, 2023)

Comparisons between temporal statistical metrics, time series stacks and phenological features derived from NASA Harmonized Landsat Sentinel-2 data for crop type mapping - Xiaomi Liu; Shuai Xie; Jiangning Yang; Lin Sun; Liangyun Liu; Qing Zhang; Chenghai Yang (Computers and Electronics in Agriculture, 2023)

Semen damage contributed over 50 % to air-pollutant-induced infertility: A prospective cohort study of 3940 men in China - Ying Guo; Qing Chen; Yu Zhan; Wenzheng Zhou; Haiyan Zhang; Niya Zhou; Huan Yang; Yi Chen; Yimeng Wang; Lei Sun; Lin Ao; Jinyi Liu; et al. (Science of The Total Environment, 2023)

Urinary Amino-PAHs in relation to diesel engine emissions and urinary mutagenicity - Junfeng (Jim) Zhang; Yuxin Zheng; Roel Vermeulen; Xing (Lucy) Liu; Yufei Dai; Wei Hu; Linchen He; Yan Lin; Dianzhi Ren; Huawei Duan; Yong Niu; Jun Xu; et al. (International Journal of Hygiene and Environmental Health, 2023)

Effects of linking group on the desalination performance of three-dimensional covalent organic framework membranes - Mengjiao Guan; Qingzhi Liu; Huiting Zhang; Qing Li; Jianan Xu; Mengmeng Cai; Weike Lin; Weina Li; Dengfeng Yang (Desalination, 2023)

The role of binary transition metal Cobalt-Nickel sulfide as an anode catalyst in specifically selection of Desulfuromonas and improved performance of microbial fuel cell - Haitao Xu; Ye Chen; Qing Wen; Cunguo Lin; Haiping Gao; Zhenghui Qiu; Liuqingying Yang; Xu Pan (Chemical Engineering Journal, 2023)

AIWW: a new nutrition-screening tool for the oncologic population - Yi-Zhong Ge; Zhen-Ming Fu; Qi Zhang; Meng-Meng Song; Guo-Tian Ruan; Xi Zhang; Xiao-Wei Zhang; Xiang-Rui Li; Kang-Ping Zhang; Meng Tang; Xiao-Yue Liu; Ming Yang; et al. (Science China Life Sciences, 2023)

Preparation of site-specific Z-scheme g-C3N4/PAN/PANI@LaFeO3 cable nanofiber membranes by coaxial electrospinning: Enhancing filtration and photocatalysis performance - Yihang Mao; Li Lin; Yuexing Chen; Mingrui Yang; Li Zhang; Xianxiang Dai; Qing He; Yuanyuan Jiang; Hui Chen; Jinqiu Liao; Yunsong Zhang; Ying Wang (Chemosphere, 2023)

Sinomenine ameliorates rheumatoid arthritis by modulating tryptophan metabolism and activating aryl hydrocarbon receptor via gut microbiota regulation - Zheng-Meng Jiang; Su-Ling Zeng; Tian-Qing Huang; Yang Lin; Fang-Fang Wang; Xing-Jiao Gao; Jing Li; Ping Li; E-Hu Liu (Science Bulletin, 2023)

The PIWI-specific insertion module helps load longer piRNAs for translational activation essential for male fertility - Xin Wang; Di-Hang Lin; Yue Yan; An-Hui Wang; Jiaoyang Liao; Qian Meng; Wen-Qing Yang; Heng Zuo; Min-Min Hua; Fengjuan Zhang; Hongwen Zhu; Hu Zhou; et al. (Science China Life Sciences, 2023)

Recent advances in luminescence and aptamer sensors based analytical determination, adsorptive removal, degradation of the tetracycline antibiotics, an overview and outlook - Ma-Lin Cui; Zi-Xuan Lin; Qing-Fan Xie; Xiao-Yan Zhang; Bing-Qing Wang; Miao-Ling Huang; Da-Peng Yang (Food Chemistry, 2023)

Gestational cadmium exposure disrupts fetal liver development via repressing estrogen biosynthesis in placental trophoblasts - Yi-Ting Fu; Jin Zhang; Wei-Bo Liu; Yu-Feng Zhang; Shuang Zhang; Lu-Lu Tan; Qing Lin; Kong-Wen Ou-Yang; Yong-Wei Xiong; Wei Chang; Hao Li; Jun-Ying Yu; et al. (Food and Chemical Toxicology, 2023)

Inchworm-Inspired soft robot with magnetic driving based on PDMS, EGaIn and NdFeB (PEN) combination - Yanfang Guan; Yansheng Liu; Qilong Wang; Hao Geng; Tangyong Cui; Yuang Hu; Qing Luo; Aonan Li; Wujie Li; Yang Lin; Lin Zhang; Guangyu Liu; et al. (Chemical Engineering Journal, 2023)

Two new species of Sarcomyxa (Agaricales) from China - Qing Cai; Wen-Fei Lin; Jian-Wei Liu; Yong Zhou; Zhu L. Yang (Mycological Progress, 2023)

ADGB variants cause asthenozoospermia and male infertility - Ronggui Qu; Zhihua Zhang; Ling Wu; Qun Li; Jian Mu; Lin Zhao; Zheng Yan; Wenjing Wang; Yang Zeng; Ruyi Liu; Jie Dong; Qiaoli Li; et al. (Human Genetics, 2023)

PM2.5 caused ferroptosis in spermatocyte via overloading iron and disrupting redox homeostasis - Jiankang Wang; Zhonghao Zhang; Fuquan Shi; Yingqing Li; Ying Tang; Chang Liu; Yimeng Wang; Jianping Chen; Xiao Jiang; Huan Yang; Lei Sun; Qing Chen; et al. (Science of The Total Environment, 2023)

Insight into the effect of pyrolysis temperature on photoreactivity of biochar-derived dissolved organic matter: Impacts of aromaticity and carbonyl groups - Hanzhuo Luo; Eydhah Almatrafi; Wenjun Wang; Yang Yang; Danlian Huang; Weiping Xiong; Min Cheng; Chengyun Zhou; Yin Zhou; Qing Lin; Guoge Fang; Guangming Zeng; et al. (Science of The Total Environment, 2023)

Biomarkers of aging - Hainan Bao; Jiani Cao; Mengting Chen; Min Chen; Wei Chen; Xiao Chen; Yanhao Chen; Yu Chen; Yutian Chen; Zhiyang Chen; Jagadish K. Chhetri; Yingjie Ding; et al. (Science China Life Sciences, 2023)

Effect of nicosulfuron on dynamic changes in the starch-sugar interconversion in sweet maize (Zea mays L.) - Jian Wang; Qing Yang; Jinling Han; Zidian He; Min Yang; Xiuping Wang; Xiaohu Lin (Environmental Science and Pollution Research, 2023)

Prevalence and Subtype Distribution of Blastocystis in Tibetan Sheep in Qinghai Province, Northwestern China - Fan Yang; Jing-min Gou; Bing-ke Yang; Jia-yue Du; Hui-zhong Yao; Mei Ren; Qing Lin (Protist, 2023)

BnIR: A multi-omics database with various tools for Brassica napus research and breeding - Zhiquan Yang; Shengbo Wang; Lulu Wei; Yiming Huang; Dongxu Liu; Yupeng Jia; Chengfang Luo; Yuchen Lin; Congyuan Liang; Yue Hu; Cheng Dai; Liang Guo; et al. (Molecular Plant, 2023)

Copper-catalyzed radical trifluoromethylalkynylation of unactivated alkenes with terminal alkynes - Yang-Qing Ren; Chang-Jiang Yang; Zhong-Liang Li; Qiang-Shuai Gu; Lin Liu; Xin-Yuan Liu (Journal of Fluorine Chemistry, 2023)

The positive effects of postbiotic (SWF concentration®) supplemented diet on skin mucus, liver, gut health, the structure and function of gut microbiota of common carp (Cyprinus carpio) fed with high-fat diet - Zhe Yu; Qiang Hao; Shu-Bin Liu; Qing-Shuang Zhang; Xing-Yu Chen; Sheng-Hui Li; Chao Ran; Ya-Lin Yang; Tsegay Teame; Zhen Zhang; Zhi-Gang Zhou (Fish & Shellfish Immunology, 2023)

To what extent the traffic restriction policies can improve its air quality? An inspiration from COVID-19 - Si-qing Xu; Hong-di He; Ming-ke Yang; Cui-lin Wu; Xing-hang Zhu; Zhong-ren Peng; Yuya Sasaki; Kenji Doi; Shinji Shimojo (Stochastic Environmental Research and Risk Assessment, 2023)

Sources, chemical components, and toxicological responses of size segregated urban air PM samples in high air pollution season in Guangzhou, China - Mo Yang; Hui-Xian Zeng; Xin-Feng Wang; Henri Hakkarainen; Ari Leskinen; Mika Komppula; Marjut Roponen; Qi-Zhen Wu; Shu-Li Xu; Li-Zi Lin; Ru-Qing Liu; Li-Wen Hu; et al. (Science of The Total Environment, 2023)

The genomes of medicinal skullcaps reveal the polyphyletic origins of clerodane diterpene biosynthesis in the family Lamiaceae - Haixiu Li; Song Wu; Ruoxi Lin; Yiren Xiao; Ana Luisa Malaco Morotti; Ya Wang; Meytal Galilee; Haowen Qin; Tao Huang; Yong Zhao; Xun Zhou; Jun Yang; et al. (Molecular Plant, 2023)

ZIF-8 sacrificial-templated hollow COF architectures enabled highly efficient enrichment, determination and regulation of food hazards from infant formulas - Lu Yang; Lin-Qing Nie; Jing Wang; Chun-Yang Li; Jin Wang; Jing-Min Liu; Shuo Wang (Food Chemistry, 2023)

Non-targeted screening for contaminants derived from food contact water-borne coatings and risk assessment based on (Q)SAR matrix - Qing-Hua Yang; Qin-Bao Lin; Jia Liao; Hong-Sheng Ma; Xiao-Fen Wei; Yue Wang; Xiaowen Xu (Food Packaging and Shelf Life, 2023)

Incorporation of oxidized debranched starch/chitosan nanoparticles for enhanced hydrophobicity of corn starch films - Qing Liu; Lin Gao; Yang Qin; Na Ji; Lei Dai; Liu Xiong; Qingjie Sun (Food Packaging and Shelf Life, 2023)

The influence of organic sources and environments on source rock deposition during the periods of Cretaceous-Eocene and Oligocene-Miocene, northern Kalimantan - Lei Lan; Youchuan Li; Zhigang Zhao; Shuchun Yang; Qing Lin; Weilai Zhang (Acta Oceanologica Sinica, 2023)

Nicosulfuron stress on the glyoxalase system and endogenous hormone content in sweet maize seedlings - Zhen-Xing Wu; Jian Wang; Xiao-Hu Lin; Qing Yang; Ting-Zhen Wang; Jian-Jian Chen; Xiang-Nan Li; Yuan Guan; Gui-Hua Lv (Environmental Science and Pollution Research, 2023)

Temporal dynamics of soil bacterial network regulate soil resistomes - Qian Xiang; Dong Zhu; Min Qiao; Xiao‐Ru Yang; Gang Li; Qing‐Lin Chen; Yong‐Guan Zhu (Environmental Microbiology, 2023)
Soil bacteria are diverse and form complicated ecological networks through various microbial interactions, which play important roles in soil multi‐functionality. However, the seasonal effects on the bacterial network, especially the relationship between bacterial network topological features and soil resistomes remains underexplored, which impedes our ability to unveil the mechanisms of the temporal‐dynamics of antibiotic resistance genes (ARGs). Here, a field investigation was conducted across four seasons at the watershed scale. We observed significant seasonal variation in bacterial networks, with lower complexity and stability in autumn, and a wider bacterial community niche in summer. Similar to bacterial communities, the co‐occurrence networks among ARGs also shift with seasonal change, particularly with respect to the topological features of the node degree, which on average was higher in summer than in the other seasons. Furthermore, the nodes with higher betweenness, stress, degree, and closeness centrality in the bacterial network showed strong relationships with the 10 major classes of ARGs. These findings highlighted the changes in the topological properties of bacterial networks that could further alter antibiotic resistance in soil. Together, our results reveal the temporal dynamics of bacterial ecological networks at the watershed scale, and provide new insights into antibiotic resistance management under environmental changes.

Sharply and simultaneously increasing pollutant accumulations in cells of organisms induced by rare earth elements in the environment of Nanjing - Qing Yang; Mengzhu Cheng; Qing Zhou; Lihong Wang; Yunlong Jiao; Yongqiang Liu; Shuya Zhang; Li Tan; Zhenhong Gu; Hong Zhu; Hongli Luo; Daozhe Lin; et al. (Chemosphere, 2023)

Mapping Chinese annual gross primary productivity with eddy covariance measurements and machine learning - Xian-Jin Zhu; Gui-Rui Yu; Zhi Chen; Wei-Kang Zhang; Lang Han; Qiu-Feng Wang; Shi-Ping Chen; Shao-Min Liu; Hui-Min Wang; Jun-Hua Yan; Jun-Lei Tan; Fa-Wei Zhang; et al. (Science of The Total Environment, 2023)

The associations of particulate matter short-term exposure and serum lipids are modified by vitamin D status: A panel study of young healthy adults - Jia-Min Li; Han-Yu Yang; Si-Han Wu; Shyamali C. Dharmage; Bin Jalaludin; Luke D. Knibbs; Michael S. Bloom; Yuming Guo; Lidia Morawska; Joachim Heinrich; Yim Steve Hung Lam; Li-Zi Lin; et al. (Environmental Pollution, 2023)

Association between long-term ambient ozone exposure and attention-deficit/hyperactivity disorder symptoms among Chinese children - Peien Zhou; Wangjian Zhang; Yu-Jie Xu; Ru-Qing Liu; Zhengmin Qian; Stephen Edward McMillin; Elizabeth Bingheim; Li-Zi Lin; Xiao-Wen Zeng; Bo-Yi Yang; Li-Wen Hu; Wen Chen; et al. (Environmental Research, 2023)

Boosting persulfate activation via paper mill sludge-based biochar for efficient degradation of bisphenol A: Inherent multiple active sites - Zhi-Juan Wang; Yang-Qian Lin; Hua-Jing Zhou; Zi-Lian Liu; Rong-Rong Miao; Xi-Meng Xu; Liang He; Qing-Qing Guan (Chemical Engineering Journal, 2023)

Effects of oxygen content on gaseous and solid products during molten salt oxidation of cation exchange resins - Yun Xue; Yue-Lin Wang; Yang-Hai Zheng; Yu-Sheng Yang; Wen-Da Xu; Yong-De Yan; Ran Zhao; Qing-Guo Zhang; Xin Liu; Fu-Qiu Ma; Mi-Lin Zhang (Environmental Science and Pollution Research, 2022)

Efficacy and Safety of Recombinant Human Prourokinase in Acute Ischemic Stroke: A Phase IIa Randomized Clinical Trial - Haiqing Song; Yuan Wang; Qingfeng Ma; Huisheng Chen; Bo Liu; Yi Yang; Jianguo Zhu; Shigang Zhao; Xiaoping Jin; Yongqiu Li; Yanyong Wang; Runxiu Zhu; et al. (Translational Stroke Research, 2022)

Development of Two Recombinase Polymerase Amplification EXO (RPA-EXO) and Lateral Flow Dipstick (RPA-LFD) Techniques for the Rapid Visual Detection of Aeromonas salmonicida - Shun Zhou; Xujia Zheng; Zongrui Yang; Qing Huang; Jingyuan Yi; Lin Su; Baoshan Guo; Yunji Xiu (Marine Biotechnology, 2022)

The particle fluxes in sediment traps from Niulang Guyot area in the Northwest Pacific Ocean - Xiuwu Sun; Jinmin Chen; Baohong Chen; Cai Lin; Yang Liu; Jiang Huang; Zhong Pan; Kaiwen Zhou; Qing He; Fangfang Kuang; Hui Lin (Acta Oceanologica Sinica, 2022)

Long‐term drought aggravates instability of alpine grassland productivity to extreme climatic event - Yun L. He; Jin S. Wang; Da S. Tian; Quan Quan; Lin Jiang; Fang F. Ma; Lu Yang; Fang Y. Zhang; Qing P. Zhou; Shu L. Niu (Ecology, 2022)
The frequency and severity of extreme weather events are increasing and expected to increase more in the future, together with global change. However, how extreme events and global change factors interactively influence community structures and ecosystem processes is largely unknown. Here, we investigated the responses of the temporal stability and resilience of aboveground net primary productivity (ANPP) of an alpine meadow to an extreme flooding event under different treatments of experimental drought and clipping. We found that ecosystems that were exposed to drought treatments for 3 years significantly decreased the temporal stability of community productivity but increased resilience to flooding, whereas their resistance to or recovery from flooding did not change. Neither clipping nor its interaction with drought altered the responses of these community stability metrics to flooding. Drought treatments significantly decreased plant species richness and asynchrony and dominant species stability, leading to a decrease in temporal stability and an increase in resilience in response to the extreme flooding event. The study also revealed that the change in species asynchrony was the dominant impact pathway determining the responses of resilience and temporal stability to flooding. Our results highlight that alpine grassland that experiences a multiyear drought may aggravate the instability of community productivity to extreme climatic events by reducing species asynchrony.

Immune responses to Vibrio vulnificus formalin‐killed vaccine and ghost vaccine in Scophthalmus maximus - Shun Zhou; Ying Li; Jingyuan Yi; Xujia Zheng; Qing Huang; Lin Su; Baoshan Guo; Zongrui Yang; Yunji Xiu (Journal of Fish Diseases, 2022)
In this research, Vibrio vulnificus formalin‐killed (FKCs) vaccine and ghost (VVGs) vaccine were successfully developed, and shown to prevent vibriosis of Scophthalmus maximus resulting from V. vulnificus. The antibody titre of FKCs and VVGs vaccine was 1: 2 8 and 1: 2 11 . The RPS of FKCs and VVGs vaccine was 60% and 80%. In order to improve the understanding of vaccine protection mechanism, transcriptome data was used to analyse the immune response of S. maximus infected with V. vulnificus after vaccination with FKCs and VVGs vaccine. In the SmCon and SmIV groups, a series of innate immune‐related genes were upregulated (such as, TLR5, Tp12, AP‐1 and IL‐1β) or downregulated (such as, CASP6 and CASP8), which suggested that the immune protection mechanism induced by inactivated vaccine was similar to that of autoimmune response. In the SmIV and SmGho group, a number of innate and adaptive immune‐related genes (such as, STAT1, IFN‐γ and MHC Ia) were activated, in which the expression of these genes was higher in SmGho, and VVGs vaccine induced stronger innate and acquired immune responses. In conclusion, the results lay a foundation for further study on the molecular mechanisms of immune protection induced by VVGs vaccine and FKCs vaccine.

Effect modification by aging on the associations of nicotine exposure with cognitive impairment among Chinese elderly - Jian Hou; Chao Huang; Bo Zhu; Wei Liu; Qing-qing Zhu; Lu Wang; Tian Li; Chun-jie Yuan; Shao-yang Lai; De-sheng Wu; Fei-qi Zhu; Jia-fei Zhang; et al. (Environmental Science and Pollution Research, 2022)

Wheat genomic study for genetic improvement of traits in China - Jun Xiao; Bao Liu; Yingyin Yao; Zifeng Guo; Haiyan Jia; Lingrang Kong; Aimin Zhang; Wujun Ma; Zhongfu Ni; Shengbao Xu; Fei Lu; Yuannian Jiao; et al. (Science China Life Sciences, 2022)

Catalytic effect of cesium on the oxidation behavior of cation exchange resins in Li2CO3-Na2CO3-K2CO3 melt - Yang-Hai Zheng; Yong-De Yan; Yun Xue; Yue-Lin Wang; Xin Liu; Wan-Sheng Mi; Qing-Guo Zhang; Yu Li; Fu-Qiu Ma; Mi-Lin Zhang; Zhi-Hao Gan; Kai Zhu (Environmental Science and Pollution Research, 2022)

Responses of photosynthesis, antioxidant enzymes, and related gene expression to nicosulfuron stress in sweet maize (Zea mays L.) - Zhen-Xing Wu; Ning-Wei Xu; Min Yang; Xiang-Ling Li; Jin-Ling Han; Xiao-Hu Lin; Qing Yang; Gui-Hua Lv; Jian Wang (Environmental Science and Pollution Research, 2022)

Production of sesquiterpene patchoulol in mitochondrion-engineered Saccharomyces cerevisiae - Xin-Yi Tao; Yang-Chen Lin; Feng-Qing Wang; Qing-Hai Liu; Yu-Shu Ma; Min Liu; Dong-Zhi Wei (Biotechnology Letters, 2022)

MAPK5 and MAPK10 overexpression influences strawberry fruit ripening, antioxidant capacity and resistance to Botrytis cinerea - Yunting Zhang; Yu Long; Yiting Liu; Min Yang; Liangxin Wang; Xiaoyang Liu; Yong Zhang; Qing Chen; Mengyao Li; Yuanxiu Lin; Haoru Tang; Ya Luo (Planta, 2022)

Environmental contamination with SARS‐CoV ‐2 in COVID ‐19 hospitals in Wuhan, China, 2020 - Wei Liu; Dingchen Li; Chaojie Yang; Fangyan Chen; Ruizhong Jia; Leili Jia; Xinyi Xia; Shanhong Fan; Qing Tan; Yuehua Ke; Yong Chen; Haifeng Li; et al. (Environmental Microbiology, 2021)
Summary Coronavirus disease 2019 (COVID‐19) pandemic has caused high number of infections and deaths of healthcare workers globally. Distribution and possible transmission route of SARS‐CoV‐2 in hospital environment should be clarified. We herein collected 431 environmental (391 surface and 40 air) samples in the intensive care unit (ICU) and general wards (GWs) of three hospitals in Wuhan, China from February 21 to March 4, 2020, and detected SARS‐CoV‐2 RNA by real‐time quantitative PCR. The viral positive rate in the contaminated areas was 17.8% (28/157), whereas there was no virus detected in the clean areas. Higher positive rate (22/59, 37.3%) was found in ICU than that in GWs (3/63, 4.8%). The surfaces of computer keyboards and mouse in the ICU were the most contaminated (8/10, 80.0%), followed by the ground (6/9, 66.7%) and outer glove (2/5, 40.0%). From 17 air samples in the contaminated areas, only one sample collected at a distance of around 30 cm from the patient was positive. Enhanced surface disinfection and hand hygiene effectively decontaminated the virus from the environment. This finding might help understand the transmission route and contamination risk of SARS‐CoV‐2 and evaluate the effectiveness of infection prevention and control measures in healthcare facilities.

A New Instrumental Array in Sichuan, China, to Monitor Vibrations and Perturbations of the Lithosphere, Atmosphere, and Ionosphere - Chieh-Hung Chen; Yang-Yi Sun; Kai Lin; Chen Zhou; Rui Xu; Haiyin Qing; Yongxin Gao; Tao Chen; Fei Wang; Huaizhong Yu; Peng Han; Chi-Chia Tang; et al. (Surveys in Geophysics, 2021)

Occurrence and removal of antibiotics, antibiotic resistance genes, and bacterial communities in hospital wastewater - Shijie Yao; Jianfeng Ye; Qing Yang; Yaru Hu; Tianyang Zhang; Lei Jiang; Salvator Munezero; Kuangfei Lin; Changzheng Cui (Environmental Science and Pollution Research, 2021)

MS1 is essential for male fertility by regulating the microsporocyte cell plate expansion in soybean - Xiaolong Fang; Xiaoyuan Sun; Xiangdong Yang; Qing Li; Chunjing Lin; Jie Xu; Wenjun Gong; Yifan Wang; Lu Liu; Limei Zhao; Baohui Liu; Jun Qin; et al. (Science China Life Sciences, 2021)

Effects of ultrasound on functional properties, structure and glycation properties of proteins: a review - Derong Lin; Qiuting Zhang; Lijuan Xiao; Yichen Huang; Zhengfang Yang; Zhijun Wu; Zongcai Tu; Wen Qin; Hong Chen; Dingtao Wu; Qing Zhang; Suqing Li (Critical Reviews in Food Science and Nutrition, 2021)

A H2O-in-zircon perspective on the heterogeneous water content of crust-derived magmas in southern Tibet - Juntong Meng; Xiaoping Xia; Lin Ma; Ziqi Jiang; Jian Xu; Zexian Cui; Qing Yang; Wanfeng Zhang; Le Zhang (Science China Earth Sciences, 2021)

QTL mapping of the genetic basis of stem diameter in soybean - Chong-Yuan Sun; Yu-Ming Yang; Lin Jia; Xiao-Qian Liu; Huan-Qing Xu; Hai-Yan Lv; Zhong-Wen Huang; Dan Zhang (Planta, 2021)

Identification of two UDP-glycosyltransferases involved in the main oleanane-type ginsenosides in Panax japonicus var. major - Jun-Rong Tang; Geng Chen; Ying-Chun Lu; Qing-Yan Tang; Wan-Ling Song; Yuan Lin; Ying Li; Su-Fang Peng; Sheng-Chao Yang; Guang-Hui Zhang; Bing Hao (Planta, 2021)

Identification of miRNA targets in eggplant in response to Verticillium dahliae by degradome sequencing - Ting Li; Nianjiao Tao; Yuanmi Lin; Min Chen; Dongli Jiao; Chunmei Xue; Wenjiao Zhu; Qing Yang (European Journal of Plant Pathology, 2021)

Cloning and characterization of rec8 gene in orange-spotted grouper (Epinephelus coioides) and Dmrt1 regulation of rec8 promoter activity - Qing Wang; Fangmei Lin; Qi He; Qifeng Huang; Xuzhuo Duan; Xiaochun Liu; Shiqiang Xiao; Huirong Yang; HuiHong Zhao (Fish Physiology and Biochemistry, 2021)

First Detection and Molecular Identification of Entamoeba in Yaks from China - Mei Ren; Fan Yang; Jing-min Gou; Pin-xue Wang; Min Zou; Xiao-hong Zhong; Qing Lin (Acta Parasitologica, 2021)

Paleoglacial and paleoclimate reconstructions during the global Last Glacial Maximum in the Longriba area, eastern Tibetan Plateau - Wei-lin Yang; Ye-song Han; Xu Peng; Ze-ze Ran; Qing Liu; Geng-nian Liu (Journal of Mountain Science, 2021)

Three pleiotropic loci associated with bone mineral density and lean body mass - Yu-Xue Zhang; Shan-Shan Zhang; Shu Ran; Yu Liu; Hong Zhang; Xiao-Lin Yang; Rong Hai; Hui Shen; Qing Tian; Hong-Wen Deng; Lei Zhang; Yu-Fang Pei (Molecular Genetics and Genomics, 2021)

Correction to: Establishment of Neurobehavioral Assessment System in Tree Shrew SCT Model - Yang-Yang Wang; Jie -Dong Wang; Lei Wang; Qi-Qin Dan; Qing- Jie Xia; Ting-Hua Wang; Liu-Lin Xiong (Journal of Molecular Neuroscience, 2021)

Identification of progranulin as a novel diagnostic biomarker for early-onset sepsis in neonates - Kai-Di Yang; Yu He; Sa Xiao; Qing Ai; Jia-Lin Yu (European Journal of Clinical Microbiology & Infectious Diseases, 2020)

Divergence in flowering time is a major component contributing to reproductive isolation between two wild rice species (Oryza rufipogon and O. nivara) - Xun Xu; Qing-Lin Meng; Mu-Fan Geng; Ning-Ning Ren; Lian Zhou; Yu-Su Du; Zhe Cai; Mei-Xia Wang; Xin Wang; Xiu-Hua Wang; Jing-Dan Han; Shuai Jiang; et al. (Science China Life Sciences, 2020)

Tectochrysin increases stress resistance and extends the lifespan of Caenorhabditis elegans via FOXO/DAF-16 - Min Lu; Lin Tan; Xiao-Gang Zhou; Zhong-Lin Yang; Qing Zhu; Jian-Ning Chen; Huai-Rong Luo; Gui-Sheng Wu (Biogerontology, 2020)

Tyrosine Hydroxylase Gene Polymorphisms Contribute to Opioid Dependence and Addiction by Affecting Promoter Region Function - Jun-lin Liu; Shao-qing Li; Feng Zhu; Yu-xiang Zhang; Ya-nan Wu; Jing-si Yang; Bao Zhang; Chun-xia Yan (NeuroMolecular Medicine, 2020)

Natural sex change in mature protogynous orange‐spotted grouper ( Epinephelus coioides ): gonadal restructuring, sex hormone shifts and gene profiles - Cheng Peng; Qing Wang; Herong Shi; Jiaxing Chen; Shuisheng Li; Huihong Zhao; Haoran Lin; Jianchun Yang; Yong Zhang (Journal of Fish Biology, 2020)
Sexual patterns of teleosts are extremely diverse and include both gonochorism and hermaphroditism. As a protogynous hermaphroditic fish, all orange‐spotted groupers ( Epinephelus coioides ) develop directly into females, and some individuals change sex to become functional males later in life. This study investigated gonadal restructuring, shifts in sex hormone levels and gene profiles of cultured mature female groupers during the first (main) breeding season of 2019 in Huizhou, China (22° 42′ 02.6″ N, 114° 32′ 10.1″ E). Analysis of gonadal restructuring revealed that females with pre‐vitellogenic ovaries underwent vitellogenesis, spawning and regression and then returned to the pre‐vitellogenic stage in the late breeding season, at which point some changed sex to become males via the intersex gonad stage. A significant decrease in the level of serum 17 β ‐estradiol (E2) was observed during ovary regression but not during sex change, whereas serum 11‐ketotestosterone (11‐KT) concentrations increased significantly during sex change with the highest concentration in newly developed males. Consistent with serum hormone changes, a significant decrease in cyp19a1a expression was observed during ovary regression but not during sex change, whereas the expression of cyp11c1 and hsd11b2 increased significantly during sex change. Interestingly, hsd11b2 but not cyp11c1 was significantly upregulated from the pre‐vitellogenic ovary stage to the early intersex gonad stage. These results suggest that a decrease in serum E2 concentration and downregulation of cyp19a1a expression are not necessary to trigger the female‐to‐male transformation, whereas increased 11‐KT concentration and upregulation of hsd11b2 expression may be key events for the initiation of sex change in the orange‐spotted grouper.

Interferon-α2b spray inhalation did not shorten virus shedding time of SARS-CoV-2 in hospitalized patients: a preliminary matched case-control study - Shao-rui Hao; Ren Yan; Shan-yan Zhang; Jiang-shan Lian; Huan Cai; Xiao-li Zhang; Lin Zheng; Hong-yu Jia; Jian-hua Hu; Guo-dong Yu; Jue-qing Gu; Chan-yuan Ye; et al. (Journal of Zhejiang University-SCIENCE B, 2020)

Two novel pleiotropic loci associated with osteoporosis and abdominal obesity - Lu Liu; Xiao-Lin Yang; Hong Zhang; Zi-Jia Zhang; Xin-Tong Wei; Gui-Juan Feng; Ju Liu; Hui-Ping Peng; Rong Hai; Hui Shen; Qing Tian; Hong-Wen Deng; et al. (Human Genetics, 2020)

Comparison of epidemiological and clinical characteristics of COVID-19 patients with and without Wuhan exposure - Jiang-shan Lian; Huan Cai; Shao-rui Hao; Xi Jin; Xiao-li Zhang; Lin Zheng; Hong-yu Jia; Jian-hua Hu; Shan-yan Zhang; Guo-dong Yu; Jue-qing Gu; Chan-yuan Ye; et al. (Journal of Zhejiang University-SCIENCE B, 2020)

The Potential Role of PKA/CREB Signaling Pathway Concerned with Gastrodin Administration on Methamphetamine-Induced Conditioned Place Preference Rats and SH-SY5Y Cell Line - Gen-Meng Yang; Lu Li; Feng-Lin Xue; Chen-Li Ma; Xiao-Feng Zeng; Yong-Na Zhao; Dong-Xian Zhang; Yang Yu; Qian-Wen Yan; Yi-Qing Zhou; Shi-Jun Hong; Li-Hua Li (Neurotoxicity Research, 2020)

ABA and sucrose co-regulate strawberry fruit ripening and show inhibition of glycolysis - Ya Luo; Cong Ge; Yajie Ling; Fan Mo; Min Yang; Leiyu Jiang; Qing Chen; Yuanxiu Lin; Bo Sun; Yong Zhang; Yan Wang; Mengyao Li; et al. (Molecular Genetics and Genomics, 2020)

Influence of simulating deep-sea environmental factors on cathodic performance of seawater battery - Yonghong Lu; Lulu Yang; Yue Zhang; Qing Zhao; Lin Sang; Fei Ding; Haibo Xu (Journal of Oceanology and Limnology, 2020)

Establishment of Neurobehavioral Assessment System in Tree Shrew SCT Model - Yang-Yang Wang; Jie-Dong Wang; Lei Wang; Qi-Qin Dan; Qing-Jie Xia; Ting-Hua Wang; Liu-Lin Xiong (Journal of Molecular Neuroscience, 2020)

Southward subduction of the Bangong-Nujiang Tethys Ocean: insights from ca. 161–129 Ma arc volcanic rocks in the north of Lhasa terrane, Tibet - Yue Tang; Qing-Guo Zhai; Pei-Yuan Hu; Sun-Lin Chung; Xu-Chang Xiao; Hai-Tao Wang; Zhi-Cai Zhu; Wei Wang; Hao Wu; Hao-Yang Lee (International Journal of Earth Sciences, 2020)

Characteristics and Prognosis of Talaromyces marneffei Infection in Non-HIV-Infected Children in Southern China - Jing Guo; Bing-Kun Li; Tian-Min Li; Fang-Lin Wei; Yu-Jiao Fu; Yan-Qing Zheng; Kai-Su Pan; Chun-Yang Huang; Cun-Wei Cao (Mycopathologia, 2019)

Hippocampal atrophy and functional connectivity disruption in cirrhotic patients with minimal hepatic encephalopathy - Weiwen Lin; Xuhui Chen; Yong-Qing Gao; Zhe-Ting Yang; Weizhu Yang; Hua-Jun Chen (Metabolic Brain Disease, 2019)

Antimicrobial and cytotoxic juglones from the immature exocarps of Juglans mandshurica - Qin Yang; Qing-Shou Yao; Yi Kuang; Yue-Zhi Zhang; Ling-Ling Feng; Lu Zhang; Lin Guo; Ze-Ping Xie; Shu-Min Zhang (Natural Product Research, 2019)

Protein glycosylation: a promising way to modify the functional properties and extend the application in food system - Qing Zhang; Lin Li; Qiuyu Lan; Meili Li; Dingtao Wu; Hong Chen; Yaowen Liu; Derong Lin; Wen Qin; Zhiqing Zhang; Jiang Liu; Wenyu Yang (Critical Reviews in Food Science and Nutrition, 2019)

Groove structure of porous hydroxyapatite scaffolds (HAS) modulates immune environment via regulating macrophages and subsequently enhances osteogenesis - Chenglong Li; Lu Yang; Xiaohua Ren; Mu Lin; Xiliang Jiang; Daonan Shen; Taotao Xu; Jing Ren; Lijuan Huang; Wei Qing; Jiajun Zheng; Yandong Mu (JBIC Journal of Biological Inorganic Chemistry, 2019)

The LRP6 functional mutation rs2302685 contributes to individual susceptibility to alcoholic liver injury related to the Wnt/β-catenin-TCF1-CYP2E1 signaling pathway - Ying Xu; Dan Chen; Xiu-Xian Lin; Qing Zhao; Jing Guo; Li-jie Chen; Wei Zhang; Jian Xiao; Guang-Hui Lian; Shi-Fang Peng; Dong Guo; Hong Yang; et al. (Archives of Toxicology, 2019)

Two Genes (ClS1 and ClF-box) Involved the Self-Incompatibility of ”Xiangshui” Lemon (Citrus limon (L.) Burm. f.) - Wei Lin; Shuwei Zhang; Feng Ding; Xinhua He; Cong Luo; Guixiang Huang; Minhphu Do; Qing Wang; Zaiyun Yang; Ling Su; Guibing Hu (Plant Molecular Biology Reporter, 2019)

Chemical composition, antioxidant, antibacterial and cytotoxic activities of essential oil of Leontopodium leontopodioides (Willd.) Beauverd - Yang Gao; Huijuanzi Rao; Ling-Jing Mao; Qing-Lin Ma (Natural Product Research, 2019)

Transcriptome analysis of Panax zingiberensis identifies genes encoding oleanolic acid glucuronosyltransferase involved in the biosynthesis of oleanane-type ginsenosides - Qing-Yan Tang; Geng Chen; Wan-Ling Song; Wei Fan; Kun-Hua Wei; Si-Mei He; Guang-Hui Zhang; Jun-Rong Tang; Ying Li; Yuan Lin; Sheng-Chao Yang (Planta, 2019)

Atorvastatin ameliorates the contractile dysfunction of the aorta induced by organ culture - Feng Zhou; Fang Rao; You-Qing Deng; Hui Yang; Su-Juan Kuang; Fei-Long Wu; Shu-Lin Wu; Yu-Mei Xue; Xiao-Mu Wu; Chun-Yu Deng (Naunyn-Schmiedeberg's Archives of Pharmacology, 2019)

Ginsenoside Compound K Regulates Amyloid β via the Nrf2/Keap1 Signaling Pathway in Mice with Scopolamine Hydrobromide-Induced Memory Impairments - Qing Yang; Jianan Lin; Huiyuan Zhang; Yingna Liu; Mo Kan; Zhiru Xiu; Xijun Chen; Xingcheng Lan; Xiaohua Li; Xiaozheng Shi; Na Li; Xiaobo Qu (Journal of Molecular Neuroscience, 2019)

The analgesic effect and possible mechanisms by which koumine alters type II collagen-induced arthritis in rats - Gui-Lin Jin; Jian Yang; Wan-Qing Chen; Jie Wang; Hong-Qiang Qiu; Ying Xu; Chang-Xi Yu (Journal of Natural Medicines, 2019)

Transcriptome Reveals Differentially Expressed Genes in Saccharum spontaneum GX83-10 Leaf Under Drought Stress - Kai-Chao Wu; Li-Ping Wei; Cheng-Mei Huang; Yuan-Wen Wei; Hui-Qing Cao; Lin Xu; Hai-Bin Luo; Sheng-Li Jiang; Zhi-Nian Deng; Yang-Rui Li (Sugar Tech, 2018)

Dominant Cutting Parameters Affecting the Specific Energy of Selected Sandstones when Using Conical Picks and the Development of Empirical Prediction Models - Xiang Wang; Qing-Feng Wang; Yun-Pei Liang; Okan Su; Lin Yang (Rock Mechanics and Rock Engineering, 2018)

pTAC10, an S1-domain-containing component of the transcriptionally active chromosome complex, is essential for plastid gene expression in Arabidopsis thaliana and is phosphorylated by chloroplast-targeted casein kinase II - Qing-Bo Yu; Tuan-Tuan Zhao; Lin-Shan Ye; Ling Cheng; Ying-Qian Wu; Chao Huang; Zhong-Nan Yang (Photosynthesis Research, 2018)

Expression of BC1 Impairs Spatial Learning and Memory in Alzheimer’s Disease Via APP Translation - Tongmei Zhang; Pei Pang; Zemin Fang; Yu Guo; Hao Li; Xinyan Li; Tian Tian; Xin Yang; Wenting Chen; Shu Shu; Na Tang; Jianhua Wu; et al. (Molecular Neurobiology, 2018)

Research progress in tofu processing: From raw materials to processing conditions - Qing Zhang; Chenzhi Wang; Bokang Li; Lin Li; Derong Lin; Hong Chen; Yaowen Liu; Suqing Li; Wen Qin; Jiang Liu; Weiguo Liu; Wenyu Yang (Critical Reviews in Food Science and Nutrition, 2018)

Isolation and Comparative Analysis of Two Na+/H+ Antiporter NHX2 Genes from Pyrus betulaefolia - Hui Li; Wei Liu; Qing-Song Yang; Jing Lin; You-Hong Chang (Plant Molecular Biology Reporter, 2018)

Microphytoplankton community structure in the western Arctic Ocean: surface layer variability of geographic and temporal considerations in summer - Yu Wang; Peng Xiang; Jian-hua Kang; You-yin Ye; Geng-ming Lin; Qing-liang Yang; Mao Lin (Hydrobiologia, 2018)

Microsatellite records for volume 10, issue 1 - Ai-Qing Yu; Chengxin Fu; Chongbo He; Fei Liu; Guo-Hua Ding; Hongman Hou; Jian Zhao; Jianmin Yang; Jiansheng Wang; Kun-ci Chen; Lan-lan Zhang; Pan Li; et al. (Conservation Genetics Resources, 2018)

Fast trace determination of nine odorant and estrogenic chloro- and bromo-phenolic compounds in real water samples through automated solid-phase extraction coupled with liquid chromatography tandem mass spectrometry - Su-fen Yuan; Ze-hua Liu; Hai-xian Lian; Chuang-tao Yang; Qing Lin; Hua Yin; Zhang Lin; Zhi Dang (Environmental Science and Pollution Research, 2018)

Climatology of cloud-base height from long-term radiosonde measurements in China - Yong Zhang; Lejian Zhang; Jianping Guo; Jinming Feng; Lijuan Cao; Yang Wang; Qing Zhou; Liangxu Li; Bai Li; Hui Xu; Lin Liu; Ning An; et al. (Advances in Atmospheric Sciences, 2018)

Comorbidity Burden of Dementia: A Hospital-Based Retrospective Study from 2003 to 2012 in Seven Cities in China - Qing-Hua Wang; Xin Wang; Xian-Le Bu; Yan Lian; Yang Xiang; Hong-Bo Luo; Hai-Qiang Zou; Jie Pu; Zhong-He Zhou; Xiao-Ping Cui; Qing-Song Wang; Xiang-Qun Shi; et al. (Neuroscience Bulletin, 2017)

Erratum to: LPS Pretreatment Provides Neuroprotective Roles in Rats with Subarachnoid Hemorrhage by Downregulating MMP9 and Caspase3 Associated with TLR4 Signaling Activation - Ting-Hua Wang; Liu-Lin Xiong; Shuai-Fen Yang; Chao You; Qing-Jie Xia; Yang Xu; Piao Zhang; Shu-Fen Wang; Jia Liu (Molecular Neurobiology, 2017)

RETRACTED ARTICLE: LPS Pretreatment Provides Neuroprotective Roles in Rats with Subarachnoid Hemorrhage by Downregulating MMP9 and Caspase3 Associated with TLR4 Signaling Activation - Ting-Hua Wang; Liu-Lin Xiong; Shuai-Fen Yang; Chao You; Qing-Jie Xia; Yang Xu; Piao Zhang; Shu-Fen Wang; Jia Liu (Molecular Neurobiology, 2017)

Apoptosis induction of colorectal cancer cells HTL-9 in vitro by the transformed products of soybean isoflavones by Ganoderma lucidum - Mei-lin Cui; Huan-yi Yang; Guo-qing He (Journal of Zhejiang University-SCIENCE B, 2017)

Molecular diversity of phenothiazines: design and synthesis of phenothiazine–dithiocarbamate hybrids as potential cell cycle blockers - Dong-Jun Fu; Ruo-Han Zhao; Jia-Huan Li; Jia-Jia Yang; Ruo-Wang Mao; Bo-Wen Wu; Ping Li; Xiao-Lin Zi; Qing-Qing Zhang; Hui-Jie Cai; Sai-Yang Zhang; Yan-Bing Zhang; et al. (Molecular Diversity, 2017)

The AMT1 family genes from Malus robusta display differential transcription features and ammonium transport abilities - Hui Li; Qing-song Yang; Wei Liu; Jing Lin; You-hong Chang (Molecular Biology Reports, 2017)

Quantitative estimation and spatial reconstruction of urban and rural construction land in Jiangsu Province, 1820–1985 - Jinyuan Xie; Xiaobin Jin; Yinan Lin; Yinong Cheng; Xuhong Yang; Qing Bai; Yinkang Zhou (Journal of Geographical Sciences, 2017)

Adjuvant effects mediated by the carbohydrate recognition domain of Agrocybe aegerita lectin interacting with avian influenza H9N2 viral surface glycosylated proteins - Li-bao Ma; Bao-yang Xu; Min Huang; Lv-hui Sun; Qing Yang; Yi-jie Chen; Ya-lin Yin; Qi-gai He; Hui Sun (Journal of Zhejiang University-SCIENCE B, 2017)

Regulatory element-based prediction identifies new susceptibility regulatory variants for osteoporosis - Shi Yao; Yan Guo; Shan-Shan Dong; Ruo-Han Hao; Xiao-Feng Chen; Yi-Xiao Chen; Jia-Bin Chen; Qing Tian; Hong-Wen Deng; Tie-Lin Yang (Human Genetics, 2017)

ACOS5 is required for primexine formation and exine pattern formation during microsporogenesis in Arabidopsis - Hui-hui Xie; Lin Chen; Fa-qing Xu; Wan-sheng Guo; Shui Wang; Zhong-nan Yang; Sen Zhang (Journal of Plant Biology, 2017)

Two new phenylpropanoids from Swertia atroviolacea and their anti-5 α -reductase activity - Hai-Yan Wu; Xue-Qing Kan; Yu Sheng; Lin-Yun Mou; Qing-Song Yang; Qiu-Feng Hu; Gan-Peng Li (Natural Product Research, 2017)

Different responses of influenza epidemic to weather factors among Shanghai, Hong Kong, and British Columbia - Xi-Ling Wang; Lin Yang; Dai-Hai He; Alice PY Chiu; Kwok-Hung Chan; King-Pan Chan; Maigeng Zhou; Chit-Ming Wong; Qing Guo; Wenbiao Hu (International Journal of Biometeorology, 2017)

Dimeric furanocoumarins from the roots of Angelica dahurica - Wan-Qing Yang; Zhi-Xiang Zhu; Yue-Lin Song; Bo-Wen Qi; Juan Wang; Cong Su; Peng-Fei Tu; She-Po Shi (Natural Product Research, 2017)

Erratum to: Lentiviral-Mediated Netrin-1 Overexpression Improves Motor and Sensory Functions in SCT Rats Associated with SYP and GAP-43 Expressions - Xue Fei Han; Yuan Zhang; Liu Lin Xiong; Yang Xu; Piao Zhang; Qing Jie Xia; Ting Hua Wang; Ying Chun Ba (Molecular Neurobiology, 2017)

Transient Receptor Potential-canonical 1 is Essential for Environmental Enrichment-Induced Cognitive Enhancement and Neurogenesis - Lai-Ling Du; Lin Wang; Xi-Fei Yang; Ping Wang; Xiao-Hong Li; Da-Min Chai; Bing-Jin Liu; Yun Cao; Wei-Qi Xu; Rong Liu; Qing Tian; Jian-Zhi Wang; et al. (Molecular Neurobiology, 2017)

Morphology and controlling factors of the longitudinal profile of gullies in the Yuanmou dry-hot valley - Lin Ding; Fa-chao Qin; Hai-dong Fang; Hui Liu; Bin Zhang; Cheng-qiang Shu; Qing-chun Deng; Gang-cai Liu; Qian-qian Yang (Journal of Mountain Science, 2017)

Naringenin ameliorates hypoxia/reoxygenation-induced endoplasmic reticulum stress-mediated apoptosis in H9c2 myocardial cells: involvement in ATF6, IRE1α and PERK signaling activation - Jia-You Tang; Ping Jin; Qing He; Lin-He Lu; Ji-Peng Ma; Wei-Lun Gao; He-Ping Bai; Jian Yang (Molecular and Cellular Biochemistry, 2017)

Combined effects of age and polymorphisms in Notch3 in the pathogenesis of cerebral infarction disease - Chun-Yu Zhu; Yue Wang; Qing-Xuan Zeng; Yu Qian; Huan Li; Zi-Xia Yang; Ya-Mei Yang; Qiong Zhang; Fei-Feng Li; Shu-Lin Liu (Metabolic Brain Disease, 2016)

Simultaneous determination of estrogenic odorant alkylphenols, chlorophenols, and their derivatives in water using online headspace solid phase microextraction coupled with gas chromatography-mass spectrometry - Su-fen Yuan; Ze-hua Liu; Hai-Xian Lian; Chuangtao Yang; Qing Lin; Hua Yin; Zhi Dang (Environmental Science and Pollution Research, 2016)

Analyzing land use characteristics of rural settlements on the urban fringe of Liangjiang New Area, Chongqing, China - Yi Wang; Guo-hua Bi; Qing-yuan Yang; Zhao-lin Wang (Journal of Mountain Science, 2016)

Ecological species groups and interspecific association of vegetation in natural recovery process at Xiejiadian landslide after 2008 Wenchuan earthquake - Qing-wei Yang; Shou-jiang Liu; Cui-hua Hu; Ye-bin Lin; Bin Zhang; Ming-liang Luo; Hui-ling Peng (Journal of Mountain Science, 2016)

PPARGC1B gene is associated with Kashin-Beck disease in Han Chinese - Yan Wen; Jingcan Hao; Xiao Xiao; Wenyu Wang; Xiong Guo; Weimin Lin; Tielin Yang; Xiaogang Liu; Hui Shen; Lijun Tan; Xiangding Chen; Qing Tian; et al. (Functional & Integrative Genomics, 2016)

Gene characterization and transcription analysis of two new ammonium transporters in pear rootstock (Pyrus betulaefolia) - Hui Li; Jin-Long Han; You-Hong Chang; Jing Lin; Qing-Song Yang (Journal of Plant Research, 2016)

Multiscale partitioning of small mammal β‐diversity provides novel insights into the Quaternary faunal history of Qinghai–Tibetan Plateau and Hengduan Mountains - Zhixin Wen; Qisen Yang; Qing Quan; Lin Xia; Deyan Ge; Xue Lv (Journal of Biogeography, 2016)
Aim To assess the validity of four hypothesized drivers (Quaternary climate, niche conservatism, contemporary climate, spatial configuration) of small mammal beta diversity in the Qinghai–Tibetan Plateau ( QTP ) and the Hengduan Mountains ( HDM ). Location QTP and HDM of China. Methods We partitioned the beta diversity of small mammals in QTP and HDM into the spatial turnover and nestedness components at the regional (longitudinal/latitudinal zones) and grid (1° × 1°) scales. Regional beta diversity was evaluated by calculating the multiple‐site dissimilarities and the distance‐dissimilarity relationships. We examined the relative effects of geographical distance, environmental difference, habitat diversity, geographical isolation and Quaternary climate stability on the beta diversity patterns. Results The overall beta diversity in all longitudinal/latitudinal zones of both regions was primarily driven by spatial turnover, longitudinal nestedness patterns were almost non‐existent in QTP . Turnover was stronger in the latitudinal direction of QTP and in the longitudinal direction of HDM , which corresponded to the general topography of each region. At the grid scale, higher turnover was primarily concentrated in mountainous areas. Turnover was highly correlated with geographical distance and environmental difference in both regions, and geographical isolation was another strong predictor of turnover in HDM . Habitat diversity independently explained most of the variation in nestedness of HDM . Main conclusions Spatial turnover is the primary cause of the small mammal beta diversity in QTP and HDM . Three non‐exclusive mechanisms including the historic effect of past glaciation, contemporary climate and spatial configuration of the landscape might act in combination to shape the beta diversity patterns in QTP and HDM , particularly the directional patterns. Our results challenge the prevailing view that the current distribution of QTP fauna is primarily explained by westward post‐glacial recolonization, and support the alternative idea that QTP retained considerable refugia and even centres of origin during the Quaternary glaciations.

Improvement of soybean transformation via Agrobacterium tumefaciens methods involving α-aminooxyacetic acid and sonication treatments enlightened by gene expression profile analysis - Yan-Min Zhang; Zi-Hui Liu; Rui-Juan Yang; Guo-Liang Li; Xiu-Lin Guo; Hua-Ning Zhang; Hong-Mei Zhang; Rui Di; Qing-Song Zhao; Meng-Chen Zhang (Plant Cell Reports, 2016)

Spatio-temporal distribution of flood disasters and analysis of influencing factors in Africa - Chan-juan Li; Yuan-qing Chai; Lin-sheng Yang; Hai-rong Li (Natural Hazards, 2016)

Infralimbic Endothelin1 Is Critical for the Modulation of Anxiety-Like Behaviors - Lin-Lin Bi; Ming Chen; Lei Pei; Shu Shu; Hui-Juan Jin; Hong-Lin Yan; Na Wei; Shan Wang; Xin Yang; Huan-Huan Yan; Meng-meng Xu; Cheng-Ye Yao; et al. (Molecular Neurobiology, 2016)

Knockdown of α-synuclein in cerebral cortex improves neural behavior associated with apoptotic inhibition and neurotrophin expression in spinal cord transected rats - You-Cui Wang; Guo-Ying Feng; Qing-Jie Xia; Yue Hu; Yang Xu; Liu-lin Xiong; Zhi-wei Chen; Hang-Ping Wang; Ting-Hua Wang; Xue Zhou (Apoptosis, 2016)

SIL1 Rescued Bip Elevation-Related Tau Hyperphosphorylation in ER Stress - Zan-Chao Liu; Jiang Chu; Li Lin; Jie Song; Lin-Na Ning; Hong-Bin Luo; Shu-Sheng Yang; Yan Shi; Qun Wang; Na Qu; Qi Zhang; Jian-Zhi Wang; et al. (Molecular Neurobiology, 2016)

Therapeutic Intervention of Learning and Memory Decays by Salidroside Stimulation of Neurogenesis in Aging - Huijuan Jin; Lei Pei; Xiaogang Shu; Xin Yang; Tianhua Yan; Yan Wu; Na Wei; Honglin Yan; Shan Wang; Chengye Yao; Dan Liu; Qing Tian; et al. (Molecular Neurobiology, 2016)

Microsatellite records for volume 8, issue 1 - Maria Cristina Arias; Stéphane Aulagnier; Erin F. Baerwald; Robert M. R. Barclay; Jacqueline Silva Batista; Rochelle R. Beasley; Rodrigo A. Bezerra; Frédéric Blanc; Eli S. Bridge; Maria Teresa Cabria; Lívia Izabela Caputo; Jie Chen; et al. (Conservation Genetics Resources, 2016)

Erratum to: Microsatellite records for volume 7, issue 4 - Rose Komugisha Basiita; J. Henrich Bruggemann; Nianhui Cai; Conchi Cáliz-Campal; Chen Chen; Jiawei Chen; L. Cizek; Pedro J. Cordero; Deborah A. Dawson; Yandong Ding; L. Drag; Anan Duan; et al. (Conservation Genetics Resources, 2016)

Exome sequencing identified FGF12 as a novel candidate gene for Kashin-Beck disease - Feng Zhang; Lanlan Dai; Weimin Lin; Wenyu Wang; Xuanzhu Liu; Jianguo Zhang; Tielin Yang; Xiaogang Liu; Hui Shen; Xiangding Chen; Lijun Tan; Qing Tian; et al. (Functional & Integrative Genomics, 2016)

Heat-induced unfolding of apo-CP43 studied by fluorescence spectroscopy and CD spectroscopy - Qing-Jie Xiao; Zai-Geng Li; Jiao Yang; Qing He; Lei Xi; Lin-Fang Du (Photosynthesis Research, 2015)

Submerged fermentation production and characterization of intracellular triterpenoids from Ganoderma lucidum using HPLC-ESI-MS - Mei-lin Cui; Huan-yi Yang; Guo-qing He (Journal of Zhejiang University-SCIENCE B, 2015)

Serum Amyloid-Beta Levels are Increased in Patients with Chronic Obstructive Pulmonary Disease - Xian-Le Bu; Guo-Qiang Cao; Lin-Lin Shen; Yang Xiang; Shu-Sheng Jiao; Yu-Hui Liu; Chi Zhu; Fan Zeng; Qing-Hua Wang; Ye-Ran Wang; Yong He; Hua-Dong Zhou; et al. (Neurotoxicity Research, 2015)

Retraction Note to: Lactoferrin promote primary rat osteoblast proliferation and differentiation via up-regulation of insulin-like growth factor-1 expression - Jian-ming Hou; Man Wu; Qing-ming Lin; Fan Lin; Ying Xue; Xu-hua Lan; En-yu Chen; Mei-li Wang; Hai-yan Yang; Feng-xiong Wang (Molecular Biology Reports, 2015)

Generation of insect-resistant and glyphosate-tolerant rice by introduction of a T-DNA containing two Bt insecticidal genes and an EPSPS gene - Qi-chao Zhao; Ming-hong Liu; Xian-wen Zhang; Chao-yang Lin; Qing Zhang; Zhi-cheng Shen (Journal of Zhejiang University-SCIENCE B, 2015)

The diversity of coral associated bacteria and the environmental factors affect their community variation - Yan-Ying Zhang; Juan Ling; Qing-Song Yang; You-Shao Wang; Cui-Ci Sun; Hong-Yan Sun; Jing-Bin Feng; Yu-Feng Jiang; Yuan-Zhou Zhang; Mei-Lin Wu; Jun-De Dong (Ecotoxicology, 2015)

Potential Neurogenesis of Human Adipose-Derived Stem Cells on Electrospun Catalpol-Loaded Composite Nanofibrous Scaffolds - Jian-Hui Guo; Yang Liu; Zheng-Jun Lv; Wen-Juan Wei; Xin Guan; Qing-Lin Guan; Zhi-Qian Leng; Jing-Yuan Zhao; Hui Miao; Jing Liu (Annals of Biomedical Engineering, 2015)

Eco-environmental vulnerability assessment for large drinking water resource: a case study of Qiandao Lake Area, China - Qing Gu; Jun Li; Jinsong Deng; Yi Lin; Ligang Ma; Chaofan Wu; Ke Wang; Yang Hong (Frontiers of Earth Science, 2015)

A γ-Glutamylcysteine Synthetase Gene from Pyrus calleryana Is Responsive to Ions and Osmotic Stresses - Hui Li; Jin-long Han; Jing Lin; Qing-song Yang; You-hong Chang (Plant Molecular Biology Reporter, 2015)

Diversity and space–time dynamics of endophytic archaea from sugar beet in the north slope of Tianshan Mountain revealed by 454 pyrosequencing and T-RFLP - YingWu Shi; MuSi TaPa; Chun Li; HongMei Yang; Tao Zhang; Yan Gao; Jian Sun; Jun Zeng; Qing Lin; ZhenHua Cao; KuEr OuTi; YuGuo Li; et al. (World Journal of Microbiology and Biotechnology, 2015)

TLR1 expression in mouse brain was increased in a KA-induced seizure model - Fa-Xiang Wang; Shi-Yong Liu; Xin Zheng; Xin Chen; Lin-Xiang Lu; Bin Chen; Xiao-yi Xiong; Hai-Feng Shu; Qing-Wu Yang; Hui Yang (Inflammation Research, 2015)

Physical‐biological coupling of N 2 fixation in the northwestern S outh C hina S ea coastal upwelling during summer - Run Zhang; Min Chen; Qing Yang; Yuanshao Lin; Huabin Mao; Yusheng Qiu; Jinlu Tong; E. Lv; Zhi Yang; Weifeng Yang; Jianping Cao (Limnology and Oceanography, 2015)
Here, we present the first combined results of N 2 fixation rates ( 15 N 2 assay), dissolved iron (dFe, 14 C assay) in the northwestern South China Sea (NWSCS) coastal upwelling region during summer. Surface N 2 fixation rate ranged between 0.1 nmol N L −1 d −1 and 5.6 nmol N L −1 d −1 (average 1.0 nmol N L −1 d −1 , n = 50) under nonbloom conditions. At a Trichodesmium bloom station, N 2 fixation rate was ∼ 3 orders of magnitude higher. Depth‐integrated N 2 fixation rate ranged between 7.5 μmol N m −2 d −1 and 163.1 μmol N m −2 d −1 (average 46.4 μmol N m −2 d −1 ). Our results indicate that N 2 fixation is unlikely limited by Fe availability in the NWSCS continental waters, instead, the coastal upwelling‐induced combined effects of physical and biological processes may have played a decisive role. With the upwelled cold, dFe‐rich, nutrient‐replete waters, nondiazotrophic phytoplankton growth would be preferentially enhanced while N 2 fixation was hindered due to relative deficiency of phosphate caused by massive phytoplankton utilization in the coastal upwelling. By comparison, N 2 fixation was notably elevated along with decreased PP in the offshore waters, probably due to a shift from P‐deficiency to N‐deficiency. Consistently, the contribution of N 2 fixation to PP (0.01–2.52%) also increased toward the open waters. As a significant external N source, summertime N 2 fixation is estimated to contribute a flux of 1.4 Gmol N to this area under nonbloom conditions. This study adds to the knowledge of N 2 fixation in the rarely studied subtropical coastal upwellings, and highlights the necessity of future comprehensive studies in such highly dynamic environments.

Associations Between ApoEε4 Carrier Status and Serum BDNF Levels—New Insights into the Molecular Mechanism of ApoEε4 Actions in Alzheimer’s Disease - Yu-Hui Liu; Shu-Sheng Jiao; Ye-Ran Wang; Xian-Le Bu; Xiu-Qing Yao; Yang Xiang; Qing-Hua Wang; Lin Wang; Juan Deng; Jing Li; Xin-Fu Zhou; Hua-Dong Zhou; et al. (Molecular Neurobiology, 2015)

ERK Is Involved in the Process of Acrosome Reaction In Vitro of the Chinese Mitten Crab, Eriocheir sinensis - Wen-Juan Sun; Ming Zhu; Yuan-Li Wang; Qing Li; Hong-Dan Yang; Ze-Lin Duan; Lin He; Qun Wang (Marine Biotechnology, 2015)

Interactions between household air pollution and GWAS-identified lung cancer susceptibility markers in the Female Lung Cancer Consortium in Asia (FLCCA) - H. Dean Hosgood; Minsun Song; Chao Agnes Hsiung; Zhihua Yin; Xiao-Ou Shu; Zhaoming Wang; Nilanjan Chatterjee; Wei Zheng; Neil Caporaso; Laurie Burdette; Meredith Yeager; Sonja I. Berndt; et al. (Human Genetics, 2015)

17β-Estradiol protects against apoptosis induced by interleukin-1β in rat nucleus pulposus cells by down-regulating MMP-3 and MMP-13 - Si-Dong Yang; Da-Long Yang; Ya-Peng Sun; Bao-Lin Wang; Lei Ma; Shi-Qing Feng; Wen-Yuan Ding (Apoptosis, 2015)

Primary succession of soil enzyme activity and heterotrophic microbial communities along the chronosequence of Tianshan Mountains No. 1 Glacier, China - Jun Zeng; Xiao-xia Wang; Kai Lou; Moniruzzaman Khan Eusufzai; Tao Zhang; Qing Lin; Ying-wu Shi; Hong-mei Yang; Zhong-qing Li (Antonie van Leeuwenhoek, 2015)

Two new truffles species, Tuber alboumbilicum and Tuber pseudobrumale from China - Shu-Hong Li; Lin-Yong Zheng; Cheng-Yi Liu; Yun Wang; Lin Li; Yong-Chang Zhao; Xiao-Lei Zhang; Mei Yang; Hai-Kuan Xiong; Yuan Qing; Li Wang; De-Qun Zhou (Mycological Progress, 2014)

Bio-beads with immobilized anaerobic bacteria, zero-valent iron, and active carbon for the removal of trichloroethane from groundwater - Ya-Zhen Zhou; Jie Yang; Xiao-Li Wang; Yue-Qing Pan; Hui Li; Dong Zhou; Yong-Di Liu; Ping Wang; Ji-Dong Gu; Qiang Lu; Yue-Feng Qiu; Kuang-Fei Lin (Environmental Science and Pollution Research, 2014)

Beneficial Effect of Acetic Acid on the Xylose Utilization and Bacterial Cellulose Production by Gluconacetobacter xylinus - Xiao-Yan Yang; Chao Huang; Hai-Jun Guo; Lian Xiong; Jun Luo; Bo Wang; Xue-Fang Chen; Xiao-Qing Lin; Xin-De Chen (Indian Journal of Microbiology, 2014)

RETRACTED ARTICLE: Lactoferrin promote primary rat osteoblast proliferation and differentiation via up-regulation of insulin-like growth factor-1 expression - Jian-ming Hou; Man Wu; Qing-ming Lin; Fan Lin; Ying Xue; Xu-hua Lan; En-yu Chen; Mei-li Wang; Hai-yan Yang; Feng-xiong Wang (Molecular Biology Reports, 2014)

MiR-200a is involved in proliferation and apoptosis in the human endometrial adenocarcinoma cell line HEC-1B by targeting the tumor suppressor PTEN - Rong Li; Jun-lin He; Xue-mei Chen; Chun-Lan Long; De-Hui Yang; Yu-Bin Ding; Hong-Bo Qi; Xue-Qing Liu (Molecular Biology Reports, 2014)

Two new ursolic acid saponins from Morina nepalensis var. alba Hand-Mazz - Zhi-feng Zhang; Lu-yang Lu; Pei Luo; Lin-sen Qing; Yuan Liu (Natural Product Research, 2013)

Continental flood basalts of the Huashan Group, northern margin of the Yangtze block – implications for the breakup of Rodinia - Qi Deng; Jian Wang; Zheng-Jiang Wang; Xuan-Ce Wang; Yan-Sheng Qiu; Qing-Xiong Yang; Qiu-Ding Du; Xiao-Zhuang Cui; Xiao-Lin Zhou (International Geology Review, 2013)

The first complete genomic characterization of an Amur virus isolate from China - Yu Zhang; Bo-Hua Liu; Fang Lin; Yong-Guo Zhang; Bing-Yin Si; Xiao-Ping Kang; Yi Hu; Jing Li; Xiao-Yan Wu; Yu-Chang Li; Qing-Yu Zhu; Yin-Hui Yang (Archives of Virology, 2013)

Molecular detection and genomic characterization of Torque teno sus virus 1 and 2 from domestic pigs in central China - Kun Li; Lin-Qing Wang; Yu-Yang Wu; An-Jun Chao; Quan-Wei Lu; Zhan-Yong Wei; Bao-An Cui; Hong-Ying Chen (Virus Genes, 2013)

Effect of the CYP2C19*2 and *3 genotypes, ABCB1 C3435T and PON1 Q192R alleles on the pharmacodynamics and adverse clinical events of clopidogrel in Chinese people after percutaneous coronary intervention - Xiao-Fang Tang; Jing Wang; Jia-Hui Zhang; Xian-Min Meng; Bo Xu; Shu-Bin Qiao; Yong-Jian Wu; Jue Chen; Yuan Wu; Ji-Lin Chen; Run-Lin Gao; Jin-Qing Yuan; et al. (European Journal of Clinical Pharmacology, 2013)

The flexible global ocean-atmosphere-land system model, Grid-point Version 2: FGOALS-g2 - Lijuan Li; Pengfei Lin; Yongqiang Yu; Bin Wang; Tianjun Zhou; Li Liu; Jiping Liu; Qing Bao; Shiming Xu; Wenyu Huang; Kun Xia; Ye Pu; et al. (Advances in Atmospheric Sciences, 2013)

The active alkaloids of Gelsemium elegans Benth. are potent anxiolytics - Ming Liu; Hui-Hui Huang; Jian Yang; Yan-Ping Su; Hong-Wei Lin; Li-Qing Lin; Wei-Jian Liao; Chang-Xi Yu (Psychopharmacology, 2013)

Suggestion of GLYAT gene underlying variation of bone size and body lean mass as revealed by a bivariate genome-wide association study - Yan-Fang Guo; Li-Shu Zhang; Yong-Jun Liu; Hong-Gang Hu; Jian Li; Qing Tian; Ping Yu; Feng Zhang; Tie-Lin Yang; Yan Guo; Xiang-Lei Peng; Meng Dai; et al. (Human Genetics, 2013)

The antidepressant effect of secoisolariciresinol, a lignan-type phytoestrogen constituent of flaxseed, on ovariectomized mice - Ying-Feng Wang; Zhi-Kun Xu; Dong-Hui Yang; Hai-Yan Yao; Bao-Shan Ku; Xiao-Qing Ma; Cheng-Zhi Wang; Shu-Lin Liu; Shao-Qing Cai (Journal of Natural Medicines, 2013)

Influence of gonadotropin-releasing hormone agonist on the effect of chemotherapy upon ovarian cancer and the prevention of chemotherapy-induced ovarian damage: an experimental study with nu/nu athymic mice - Qiong-yan Lin; Yi-feng Wang; Hui-nan Weng; Xiu-jie Sheng; Qing-ping Jiang; Zhi-ying Yang (Journal of Zhejiang University-SCIENCE B, 2012)

Influence of UGT genetic polymorphism on the interindividual variability in mitiglinide pharmacokinetic in Chinese - Jing-feng Xu; Zhan-qing Wang; Chen-xia Yan; Qian Xu; Lin Xu; Gang-tao Zhao; Yong-ge Yang (Medicinal Chemistry Research, 2012)

Genetic variant in TP63 on locus 3q28 is associated with risk of lung adenocarcinoma among never-smoking females in Asia - H. Dean Hosgood; Wen-Chang Wang; Yun-Chul Hong; Jiu-Cun Wang; Kexin Chen; I-Shou Chang; Chien-Jen Chen; Daru Lu; Zhihua Yin; Chen Wu; Wei Zheng; Biyun Qian; et al. (Human Genetics, 2012)

Biodegradation of bensulfuron-methyl and its effect on bacterial community in paddy soils - Xiao-Yan Lin; Yu-Yi Yang; Yu-Hua Zhao; Qing-Lin Fu (Ecotoxicology, 2012)

Novel phosphatidylinositol 3-kinase inhibitor NVP-BKM120 induces apoptosis in myeloma cells and shows synergistic anti-myeloma activity with dexamethasone - Yuhuan Zheng; Jing Yang; Jianfei Qian; Liang Zhang; Yong Lu; Haiyan Li; Heather Lin; Yongsheng Lan; Zhiqiang Liu; Jin He; Sungyoul Hong; Sheeba Thomas; et al. (Journal of Molecular Medicine, 2012)

TFF3 mediated induction of VEGF via hypoxia in human gastric cancer SGC-7901 cells - Bayasi Guleng; Jia Han; Jin-Qiu Yang; Qing-Wen Huang; Jian-Kun Huang; Xiao-Ning Yang; Jing-Jing Liu; Jian-Lin Ren (Molecular Biology Reports, 2012)

Genome-wide association study identifies HMGN3 locus for spine bone size variation in Chinese - Shu-Feng Lei; Hui Shen; Tie-Lin Yang; Yan Guo; Shan-Shan Dong; Xiang-Hong Xu; Fei-Yan Deng; Qing Tian; Yong-Jun Liu; Yao-Zhong Liu; Jian Li; Hong-Wen Deng (Human Genetics, 2012)

Molecular cloning and its expression of trachealess gene (As-trh) during development in brine shrimp, Artemia sinica - Jia-Qing Wang; Lin Hou; Nan Yi; Riu-Feng Zhang; Xiang-Yang Zou; Qin Xiao; Ran Guo (Molecular Biology Reports, 2012)

Isolation and identification of an acetoin high production bacterium that can reverse transform 2,3-butanediol to acetoin at the decline phase of fermentation - Xian Zhang; Tao-wei Yang; Qing Lin; Mei-juan Xu; Hai-feng Xia; Zheng-hong Xu; Hua-zhong Li; Zhi-ming Rao (World Journal of Microbiology and Biotechnology, 2011)

The unsaturation of phosphatidylglycerol in thylakoid membrane alleviates PSII photoinhibition under chilling stress - Xiao-lin Sun; Sha Yang; Li-Yan Wang; Qiu-Yu Zhang; Shi-Jie Zhao; Qing-Wei Meng (Plant Cell Reports, 2011)

A Proteomic Analysis of Leaf Responses to Enhanced Ultraviolet-B Radiation in Two Rice (Oryza sativa L.) Cultivars Differing in UV Sensitivity - Xing-Chun Wu; Chang-Xun Fang; Jin-Yang Chen; Qing-Shui Wang; Ting Chen; Wen-Xiong Lin; Zhong-Liang Huang (Journal of Plant Biology, 2011)

Common genetic variation in the 3′-untranslated region of gonadotropin-releasing hormone receptor regulates gene expression in cella and is associated with thyroid function, insulin secretion as well as insulin sensitivity in polycystic ovary syndrome patients - Qiaoli Li; Guizhong Yang; Ying Wang; Xiaoping Zhang; Qing Sang; Huan Wang; Xinzhi Zhao; Qinghe Xing; Lin He; Lei Wang (Human Genetics, 2011)

Mesenchymal stem cells require integrin β1 for directed migration induced by osteopontin in vitro - Chengyu Zou; Guanbin Song; Qing Luo; Lin Yuan; Li Yang (In Vitro Cellular & Developmental Biology - Animal, 2011)

Atypical Class 1 Integron Coexists with Class 1 and Class 2 Integrons in Multi-Drug Resistant Shigella flexneri Isolates from China - Jing Yuan Zhu; Guang Cai Duan; Hai Yan Yang; Qing Tang Fan; Yuan Lin Xi (Current Microbiology, 2011)

Platelet adhesion and fusion to endothelial cell facilitate the metastasis of tumor cell in hypoxia-reoxygenation condition - Na Zhang; Wen-Jian Zhang; Han-Qing Cai; Hong-Lin Liu; Liang Peng; Cheng-Hui Li; Li-Ya Ye; Shi-Qing Xu; Zhi-Hua Yang; Jin-Ning Lou (Clinical & Experimental Metastasis, 2011)

Cloning and characterization of a potato TFL1 gene involved in tuberization regulation - Jian-Lin Guo; Chun-Lin Yu; Chun-Yuan Fan; Qi-Neng Lu; Jing-Ming Yin; Yun-Feng Zhang; Qing Yang (Plant Cell, Tissue and Organ Culture (PCTOC), 2010)

Genetic analysis and characterization of a new maize association mapping panel for quantitative trait loci dissection - Xiaohong Yang; Jianbing Yan; Trushar Shah; Marilyn L. Warburton; Qing Li; Lin Li; Yufeng Gao; Yuchao Chai; Zhiyuan Fu; Yi Zhou; Shutu Xu; Guanghong Bai; et al. (Theoretical and Applied Genetics, 2010)

Novel microRNAs in silkworm (Bombyx mori) - Yimei Cai; Xiaomin Yu; Qing Zhou; Caixia Yu; Haiyan Hu; Jiucheng Liu; Hongbin Lin; Jin Yang; Bing Zhang; Peng Cui; Songnian Hu; Jun Yu (Functional & Integrative Genomics, 2010)

A New Phosphorimetry for the Determination of Trace Alkaline Phosphatase Using Multi-wall Carbon Nanotubes and Its Diagnosis of Human Diseases - Jia-Ming Liu; Ying Rao; Li Chen; Xin-Xing Wang; Li-Ping Lin; Chang-Qing Lin; Li-Hong Zhang; Ying Ou-Yang (Journal of Fluorescence, 2010)

On the conservation biology of a Chinese population of the birdwing Troides aeacus (Lepidoptera: Papilionidae) - Xiu-shan Li; You-qing Luo; Ya-lin Zhang; Oliver Schweiger; Josef Settele; Qing-sen Yang (Journal of Insect Conservation, 2010)

Subtype identification of the novel A H1N1 and other human influenza A viruses using an oligonucleotide microarray - Xiaoping Kang; Yongqiang Li; Honghe Sun; Weili Wu; Hong Liu; Fang Lin; Chenfeng Qing; Guohui Chang; Qingyu Zhu; Weijun Chen; Yinhui Yang (Archives of Virology, 2010)

Involvement of the ornithine decarboxylase/polyamine system in precondition-induced cardioprotection through an interaction with PKC in rat hearts - Ya-Jun Zhao; Wei-Hua Zhang; Chang-Qing Xu; Hong-Zhu Li; Li-Na Wang; Hong Li; Yi-Hua Sun; Yan Lin; Li-Ping Han; Li Zhang; Yie Tian; Rui Wang; et al. (Molecular and Cellular Biochemistry, 2009)

Effect of PARP-1 deficiency on DNA damage and repair in human bronchial epithelial cells exposed to Benzo(a)pyrene - Gong-hua Tao; Lin-qing Yang; Chun-mei Gong; Hai-yan Huang; Jian-dong Liu; Jian-jun Liu; Jian-hui Yuan; Wen Chen; Zhi-xiong Zhuang (Molecular Biology Reports, 2009)

An investigation of hormesis of trichloroethylene in L-02 liver cells by differential proteomic analysis - Hai-Yan Huang; Jian-Jun Liu; Ren-Rong Xi; Xiu-Mei Xing; Jian-Hui Yuan; Lin-Qing Yang; Gong-Hua Tao; Chun-Mei Gong; Zhi-Xiong Zhuang (Molecular Biology Reports, 2009)

Human papillomavirus type-distribution in cervical cancer in China: the importance of HPV 16 and 18 - Wen Chen; Xun Zhang; Anco Molijn; David Jenkins; Ju-Fang Shi; Wim Quint; Johannes E. Schmidt; Ping Wang; Yu-Ling Liu; Lian-Kun Li; Hong Shi; Ji-Hong Liu; et al. (Cancer Causes & Control, 2009)

Toxicity of lead, cadmium and mercury on embryogenesis, survival, growth and metamorphosis of Meretrix meretrix larvae - Qing Wang; Baozhong Liu; Hongsheng Yang; Xiaoyu Wang; Zhihua Lin (Ecotoxicology, 2009)

Validation of eight names of Chinese taxa in Ranunculaceae, Rosaceae and Scrophulariaceae - Qi Lin; Miao Sun; Qian Sun; Shu-Qing Bei; Hong-Li Li; Zhi-Rong Yang (Kew Bulletin, 2009)

Damage and conservation of the high cliff on the Northern area of Dunhuang Mogao Grottoes, China - Qing-lin Guo; Xu-dong Wang; Hu-yuan Zhang; Zui-xiong Li; Shan-long Yang (Landslides, 2009)

Adenovirus-mediated wild-type p53 gene transfer in combination with bronchial arterial infusion for treatment of advanced non-small-cell lung cancer, one year follow-up - Yong-song Guan; Yuan Liu; Qing Zou; Qing He; Zi La; Lin Yang; Ying Hu (Journal of Zhejiang University-SCIENCE B, 2009)

A cell strain cloned from Spodoptera exigua cell line (IOZCAS-Spex-II) highly susceptible to S. exigua nucleopolyhedrovirus infection - Huan Zhang; Yong-an Zhang; Qilian Qin; Xuan Li; Lin Miao; Yuzhu Wang; Liangjian Qu; Aijun Zhang; Qing Yang (In Vitro Cellular & Developmental Biology - Animal, 2009)

Digenic inheritance of non-syndromic deafness caused by mutations at the gap junction proteins Cx26 and Cx31 - Xue-Zhong Liu; Yongyi Yuan; Denise Yan; Emilie Hong Ding; Xiao Mei Ouyang; Yu Fei; Wenxue Tang; Huijun Yuan; Qing Chang; Li Lin Du; Xin Zhang; Guojian Wang; et al. (Human Genetics, 2009)

Molecular Cloning and Expression Analysis of a LFY Homologous Gene from Potato - Jian-lin Guo; Qing Yang (Plant Molecular Biology Reporter, 2008)

Effect of drought and low light on growth and enzymatic antioxidant system of Picea asperata seedlings - Yan Yang; Chao Han; Qing Liu; Bo Lin; Jianwen Wang (Acta Physiologiae Plantarum, 2008)

Methylenetetrahydrofolate reductase (MTHFR) C677T and A1298C polymorphisms and the risk of primary Hepatocellular Carcinoma (HCC) in a Chinese population - Li-Na Mu; Wei Cao; Zuo-Feng Zhang; Lin Cai; Qing-Wu Jiang; Nai-Chieh You; Binh Yang Goldstein; Guo-Rong Wei; Chuan-Wei Chen; Qing-Yi Lu; Xue-Fu Zhou; Bao-Guo Ding; et al. (Cancer Causes & Control, 2007)

Molecular Cloning and Expression Analysis of the Myostatin Gene in Sea Perch (Lateolabrax japonicus) - Han-Qing Ye; Song-Lin Chen; Zhen-Xia Sha; Yang Liu (Marine Biotechnology, 2007)

Pluripotency and Chimera Competence of an Embryonic Stem Cell Line from the Sea Perch (Lateolabrax japonicus) - Song-Lin Chen; Zhen-Xia Sha; Han-Qing Ye; Yang Liu; Yong-Sheng Tian; Yunhan Hong; Qi-Sheng Tang (Marine Biotechnology, 2007)

Identification ofporphyra lines (rhodophyta) by AFLP DNA fingerprinting and molecular markers - Jian Wei Sun; Min De Jin; Chun Jiang Zhou; Qing Kai Yang; Man Li Weng; Lin De Duan; Pu Xu; Jia Hai Ma; Bin Wang (Plant Molecular Biology Reporter, 2005)

Expression and production of bioactive human interleukin-18 in transgenic tobacco plants - Bin Zhang; Ying-Hua Yang; Yong-Ming Lin; Qing Rao; Guo-Guang Zheng; Ke-Fu Wu (Biotechnology Letters, 2003)

The extent and distribution of linkage disequilibrium in a multi-hierarchic outbred canine pedigree - Xiang-Yang Lou; Rory J. Todhunter; Min Lin; Qing Lu; Tian Liu; Zuoheng Wang; Stuart P. Bliss; George Casella; Gregory M. Acland; George Lust; Rongling Wu (Mammalian Genome, 2003)

Contributory presentations/posters - N. Manoj; V. R. Srinivas; A. Surolia; M. Vijayan; K. Suguna; R. Ravishankar; K. Suguna; A. Surolia; M. Vijayan; R. Schwarzenbacher; K. Zeth; Diederichs; et al. (Journal of Biosciences, 1999)